Seismic characteristics, distribution and origin of shallow gas on the continental shelf offshore the Pearl River Estuary, northern South China Sea - Jian Li; Wei Li; Tiago M. Alves; Yingci Feng; Jie Sun; Yantao Yao; Jiaxian Huang; Pin Wang; Qinqin Tang; Wenhuan Zhan (Marine Geology, 2026)

The critical x[I/L]xbS motif in adaptor proteins, MAVS, MITA, and TRIF contributes to type I IFN production and antiviral immune response in fish - Xue Yun Peng; Jing Hou; Bo Li; Chuan Yun Zhang; Lin Huang; Lan Hao Liu; Nan Li; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

PoGPx-7, a glutathione peroxidase homolog from teleosts, exhibits bactericidal activity and activates host immune cells against bacterial infection - Xin-yi Jiang; Xue-pin Han; Jia-hang Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2026)

A heparan-like glycosaminoglycan from the white jade snail: Precise structural elucidation, alkaline-induced artificial changes, and non-anticoagulant heparanase inhibition - Pin Wang; Na Gao; Qijiang Mao; Lutan Zhou; Yu Wang; Ying Pan; Fengyun Wu; Penghao Kang; Zanyang Min; Yujun Ma; Huifang Sun; Xiang Shi; et al. (Carbohydrate Polymers, 2026)

Development of magnetic solid-phase extraction with magnetic graphene oxide composite nanospheres for sensitive determination of perfluoroalkyl substances in tea beverages - Xin-Li Song; Tong Sun; Ke-Chao Liao; Hui Lv; Pin-Pin Wang; Dong-Dong Wang; Yan Lu; Lin Li (Analytica Chimica Acta, 2026)

Spatially distributed modeling of biofilm-induced hydrodynamic evolution in porous media - Hongcheng Zhang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Wang Kai Tong; Jia Jie Zou; Min-tian Gao; Zhi Li; Xihua Wang; Yalei Zhang; Kah Hon Leong; Swee Pin Yeap; et al. (Journal of Hydrology, 2026)

Regulating interface charge separation to unlock photocatalytic non-radical pathways: Construction of BiOCl/COF S-scheme heterojunction for efficient antibiotic remediation - Hailan Qin; Siyuan Di; Min Liu; Qiuyue Zhang; Pin Chen; Zihan Li; Shukui Zhu (Journal of Cleaner Production, 2026)

Integrative single-cell sequencing and environmental metabarcoding reveals genetic complexity and hidden diversity of the dinoflagellate Tripos (Dinophyceae) - Yingchao Li; Xianliang Huang; Haina Du; Xiangxiang Ding; Zhiyuan Gong; Po Teen Lim; Chui Pin Leaw; Nansheng Chen (Harmful Algae, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Elevated CO2 and temperature reshape soybean chemistry and drive physiological and life-history trade-offs in the beet webworm Loxostege sticticalis - Jingxian Zhou; Shuqi Ren; Pin Li; Sandhya Samarasinghe; Xingfu Jiang; Guijun Wan; Fajun Chen (Journal of Pest Science, 2026)

A comparative study of methods for quantifying sand-sized sediment grain textural parameters - Xiaotian Shen; Xing Jian; Wei Zhang; Ruolan Liao; Dongming Hong; Chao Li; Shaohua Zhao; James T. Liu; Yuan-Pin Chang (Sedimentary Geology, 2026)

Shift of algal symbiont communities in the coral Acropora digitifera: Shuffling and switching during thermal stress and recovery - Li Keat Lee; Chui Pin Leaw; Haifeng Gu; Po Teen Lim; Chun Hong Tan (Regional Studies in Marine Science, 2026)

Effects of dietary rumen-protected bile acids on muscle fiber composition and drip loss in Hu sheep (Ovis aries): insights from transcriptomic and metabolomic analyses - Zhe Wang; Manman Hou; Dan Hu; Jie Huang; Qi Liu; Pin Song; Yue Chen; Pengnan Chen; Yuyang Yin; Aizhi Cao; Yufeng Li; Yingdong Ni (Food Bioscience, 2026)

Cyprinid herpesvirus 2 (CyHV-2) ORF53 inhibits NF-κB signalling by targeting p65 degradation - Chuan Yun Zhang; Zheng Liu; An Ning Pang; Jia Yi Li; Bo Li; Nan Li; Lan Hao Liu; Pin Nie; Shan Nan Chen (Fish & Shellfish Immunology, 2026)

Functional characterization of IRF2 and IRF2a in Japanese eel (Anguilla japonica) identifies dual pathways suppressing interferon responses - Haijun Qin; Dongli Li; Gejie Zhao; Pin Nie; Wenshu Huang; Bei Huang (Fish & Shellfish Immunology, 2026)

Role of Mesoscale Eddies in Modulating Sea Surface Temperature off the Southeast Atlantic Coast Based on a Regional Ocean Model - Pin Li; Shidong Liu (Journal of Ocean University of China, 2026)

Effects of N-carbamylglutamate supplementation on growth, serum biochemistry, antioxidant capacity, immune function, hormonal profile, and reproductive performance in rabbits under chronic heat stress conditions - Pin Zhai; Jie Yang; Feng Qin; Yao Yao; Le Shao; Jian Li; Xia Zhang (Animal Reproduction Science, 2026)

Type I IFNs, IFNc, IFNd1, IFNd2, IFNh, and type II IFNs, IFN-γ and IFN-γrel, and their possible receptors with the identification of two variants of IFNc and IFNh in turbot (Scophthalmus maximus) - Bo Li; Meng Xin Yan; Yu Hang Deng; Xiao Qian Jiao; Shan Nan Chen; Xu Jia Zhang; Jia Le Chen; Xue Yun Peng; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Changes in decomposition rates and nutrients of leaf litter and fine roots in urban tree species under ozone pollution - Xiaofan Hou; Pin Li; Yuqian Sun; Chenhan Ma; Jing Fu; Weixia Huang; Zhuoran Zou (Urban Forestry & Urban Greening, 2026)

Toward sustainable utilization of high-iron red mud: A novel calcification-biomassification process for iron enrichment and magnetic recovery - Xingjian Wang; Yiyong Wang; Tingan Zhang; Zhiyu Fan; Zhe Ning; Pin Shao; Jidong Li (Process Safety and Environmental Protection, 2026)

Cordycepin-mediated protection against bisphenol A–induced male reproductive toxicity via PI3K/mTOR/HIF-1α signaling - Wenjuan Yang; Jiang Guo; Zhaorui Shuai; Shuai Han; Xuguang Jing; Hui Long; Nan Li; Yanni Zhao; Pin Gong; Yuxi Guo (Food Research International, 2026)

Numerical analysis of the interaction mechanism between the dual-row jet hydraulic mining collector and deep-sea sediment - Pin-Jian Wang; Li Li; Jia-Bin Wu (Computers and Geotechnics, 2026)

BRI3 Orchestrates Lipid Metabolism and Autophagy in Glioblastoma: Implications for Tumor Cell Resilience - Jun Chen; Pin Zuo; Situo Kuang; Ping Li; Xiaoquan Li; Dong Zhan (Biochemical Genetics, 2026)

Structure-Constrained Prior Ensembles for ES-MDA Post-Stack Acoustic Impedance Inversion - Zhi-fang Ran; Yin-quan Hao; Pin Zhang; Weiwei Gu; Guo-fa Li (Applied Geophysics, 2026)

Applicability of the Richards equation in infiltration simulation: A comparative study with the two-phase flow model - Hongcheng Zhang; Zhi Li; Chaomeng Dai; Jiajie Zou; Swee Pin Yeap; Kah Hon Leong; Jixiang Li; Jiajun Hu; Mintian Gao (Journal of Hydrology, 2026)

WS2-modified schwertmannite for highly efficient dye wastewater degradation via enhanced Fe cycle in heterogeneous Fenton-like catalysis - Kun Feng; Shuping Zhang; Neng Tao; Zhiyi Sun; Xianqiang Kong; Yuanyu Tan; Xuhao Liu; Lixiang Zhou; Pin Zhou; Yongjun Shen; Ting Li (Journal of Environmental Sciences, 2026)

Simultaneous removal of fluoride and disinfection by-product precursors through Zr salt enhanced coagulation - Zhanghan Li; Pin Wang; Cheng Ye; Jiacheng Luo; Yayun Zhang; Wenhai Chu (Journal of Environmental Sciences, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Heteroatom bridging chemistries enabling fast polysulfide redox and stable lithium deposition - Guangfeng Zeng; Ruiqing Luo; Yumei Qin; Xue Li; Fangting Xie; Jiajia Wang; Shulong Wang; Jingru Liang; Zhiqi Ma; Duming Wei; Qi-Pin Qin; Xiang-Long Huang (Chemical Engineering Journal, 2026)

Design and verification of a microbial consortium with an anchoring-interface enhancement strategy for efficient PAHs degradation in groundwater - Wang Kai Tong; Jiajun Hu; Chaomeng Dai; Jia Jie Zou; Han Tang; Piao Yi Jiang; Min-tian Gao; Jixiang Li; Xihua Wang; Yalei Zhang; Ken-Lin Chang; Kah Hon Leong; et al. (Water Research, 2026)

Formation and cytotoxicity of drinking water disinfection byproducts in oxidation processes followed by chlorine and chloramine disinfection - Pin Hou; Ziqi Li; Feiyu Zhai; Yunsi Liu; Chao Liu (Journal of Environmental Chemical Engineering, 2026)

Treating waste with waste: Efficient recovery of sodium, aluminum, and iron from high-iron red mud by Calcification-Biomassification process - Xingjian Wang; Yiyong Wang; Tingan Zhang; Zhiyu Fan; Zhe Ning; Pin Shao; Jidong Li (Journal of Environmental Chemical Engineering, 2026)

Sea buckthorn for future foods: bioactive mechanisms, synthetic biology, and precision delivery systems - Nan Li; Peidong Fan; Lulu Wang; Luole Feng; Hui Long; Wenjuan Yang; Jing Wang; Yanni Zhao; Huan Liu; Yuxi Guo; Pin Gong (Food Research International, 2026)

Multi-target antidiabetic peptides from highland barley (Qingke): Identification, molecular docking, and inhibitory mechanisms against α-amylase, α-glucosidase, and DPP-IV - Juan Li; Muyan Ma; Feng Liang; Yan Du; Wenju Zhou; Pin Ma; Falin Zhang; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li (Food Chemistry, 2026)

Immunomodulatory mechanism of Pleurotus eryngii polysaccharides in acrylamide-induced mice via the P2X7-NLRP3 pathway, metabolic homeostasis and gut microbiota - Jing Wang; Xiuxiu Liu; Dongliang Jin; Man Wang; Nan Zhang; Yanni Zhao; Wenjuan Yang; Nan Li; Xuefeng Chen; Pin Gong (Food Bioscience, 2026)

Mitigating Dyeing Industry Water Pollution Through Advances in Chitosan-Based Adsorbents - Swee Pin Yeap; Yvonne Ang; Shuen Lam; Swee Sen Teo; Lai Huat Lim; Li Sze Lai; Hui Suan Ng; Zeinab Abbas Jawad; Kah Hon Leong; Zaher Mundher Yaseen (Water Conservation Science and Engineering, 2026)

Electrochemical activation of peroxymonosulfate with a boron-doped diamond anode boosts short-chain fatty acid production from waste activated sludge - Kexin Li; Zhendong Lei; Yujia Zhang; Jinling He; Ming Zheng; Ai Zhang; Pin Gao; Xiang Li; Gang Xue (Water Research, 2026)

A CPTu-based method for evaluating consolidation characteristics of under-consolidated soils - Yu-cheng Li; Pin-Qiang Mo; Guojun Cai; Zhao Lu; Yan Zhuang; Hai-Sui Yu (Ocean Engineering, 2026)

Microalgae, sunlight, and starch: low cell concentration is optimal for outdoor production under nutrient stress - A. Six; P. Chambonnière; P. Alvarez; S. Fon-Sing; C. Lancelon-Pin; J.-L. Putaux; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Bioresource Technology, 2026)

Correction: Impact of the Benguela coastal low-level jet on the southeast tropical Atlantic SST bias in a regional ocean model - Jaison Kurian; Pin Li; Ping Chang; Christina M. Patricola-DiRosario; Justin Small (Climate Dynamics, 2026)

Provenance evolution of Late Mesozoic clastic rocks in the Qamdo Basin of eastern Qinghai-Tibet Plateau: Sedimentary response to the Lhasa and Qiangtang terranes collision - Changzhong Li; Weiliang Miao; Xiying Zhang; Xiaochen Ma; Pin Gao; Huanen Gu; Dengxian Zhu (Gondwana Research, 2026)

Consolidation characteristics of diatomaceous soil in coastal reclamations revealed by CPTu tests - Pin-Qiang Mo; Yu-cheng Li; Guojun Cai; Qiuzhu Ma; Hai-Sui Yu (Engineering Geology, 2026)

Targeted degradation of emerging pollutants based on specific recognition and ROS confinement effects of molecularly imprinted cavities - Jun Bo Zhang; Xu Jiang; Chaomeng Dai; Jixiang Li; Jiajun Hu; Min-tian Gao; Xueji You; Hongcheng Zhang; Shunyang Li; Peng Qiu; Zhu Zhu; Xihua Wang; et al. (Chemical Engineering Journal, 2026)

Electrocatalytic degradation of norfloxacin using biochar electrode derived from oily sludge: Synergistic effects of hydrothermal and pyrolytic treatment - Quxin Cong; Rui Jia; Juan Zhou; Lei Li; Pin Gao (Chemical Engineering Journal, 2026)

Biomimetic microneedle patch integrating ROS-scavenging nanoceria, anti-inflammatory phytochemical, and macrophage-membrane-coated nanoparticles for local hepatic therapy of endotoxemia - Bingwen Zhu; Chang Sun; Dongrong Luo; Zhongliang Zhang; Linguo Cao; Tao Bi; Aolin Jiang; Yuying Liang; Zehui Jiang; Haihua Luo; Pin Jiang; Shaoqing Liu; et al. (Chemical Engineering Journal, 2026)

Soil microbiomes in urban green spaces: Foundation of ecosystem functions and human health - Xiao-Tong Zhu; Xi-Lin Yuan; Pin Li; Congcong Shen (Soil Ecology Letters, 2026)

Experimental investigation and characterization of the vibration fatigue S-N curve for small-diameter 316L stainless steel butt-welded pipes - Ning Li; Hongbo Gao; Lei Lin; Pin Li; Shuai Zhou; Han Liu; Changning Li; Decheng Xu; Yin Liu; Zhilin Chen (Annals of Nuclear Energy, 2026)

A novel single-cell communication framework combining multi-omics reveals neuro-viral pathogenesis in fish - Yi-Fan Liu; Teng-Fei He; Zhi-Wen Zhao; Bao-Sheng Wu; Ying Liang; Lin-Miao Li; Jin-Ping Chen; Ye-Pin Yu (Marine Life Science & Technology, 2026)

Beyond simple inhibition: Unveiling the non-monotonic impact and multi-level mechanisms of aged microplastics on sludge anaerobic digestion - Jinling He; Kexin Li; Xianbao Xu; Yongquan Zhou; Ai Zhang; Pin Gao; Xiang Li; Gang Xue; Yanan Liu (Water Research, 2026)

Insecticide resistance monitoring and identification of ryanodine receptor mutations driving diamide resistance in Cnaphalocrocis medinalis - Hong-Shuang Li; Pin-Xuan Lin; Meng-Zhen Wang; Bei-Bei Dong; Cong-Fen Gao; Shun-Fan Wu (Pesticide Biochemistry and Physiology, 2026)

Evaluating post-fire watershed response to varying burn severity and precipitation regimes using fully-distributed and integrated hydrologic models - Zhi Li; Bing Li; Peishi Jiang; Glenn E. Hammond; Pin Shuai; Faria T. Zahura; Ethan T. Coon; Xingyuan Chen (Journal of Hydrology, 2026)

Characterization of monoclonal antibody against IgM and phagocytic function of IgM+ B cells in snakehead (Channa argus) - Peng Fei Mu; Zhe Wang; Qi Li; Qiu Hua Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Genomic, transcriptional and proteomic clarification of fathead minnow and common carp composition in epithelioma papulosum cyprini (EPC) cell line - Bo Li; Jing Hao Yuan; Yu Hang Deng; Shan Nan Chen; Meng Yao Ji; Xu Jia Zhang; Yang Liu; Zhen Gan; Pin Nie; Lan Hao Liu (Fish & Shellfish Immunology, 2026)

Industrial relocation: its heterogeneous effects on photovoltaic development in China - Pin Li; Jinsuo Zhang; Shaohui Zou; Jing Xiong; Hong Liu; Lei Zhou (Energy Policy, 2026)

Soil nutrient heterogeneity induces foraging behavior but does not improve overall growth performance in six bamboo species - Lin-Xuan He; Li-Li Zheng; Jia-Yu Zhang; Xiao-Mei Zhang; Jing-Pin Lei; Mai-He Li; Fei-Hai Yu (Plant and Soil, 2026)

Site-specific heterogeneity overrides park-type effects in shaping divergent phyllosphere and rhizosphere microbiomes across urban green spaces - Yun Li; Pin Li; Xiaofan Hou; Chenhan Ma; Yushu Tian; Qiannan Lin (Plant and Soil, 2026)

Anti-cancer effects of Psoralea corylifolia: insights into cancer hallmarks - Pin-Rong Chen; Tz-Syuan Su; Kun-Che Chang; Chien-Chih Chiu; Shu-Pin Huang; Hsin-Chih Yeh; Shu-Chi Wang; Chia-Yang Li (Phytochemistry Reviews, 2026)

Effects of Shifts in Bacterial Community on Improving Water Quality and Growth Performance of Pacific Whiteleg Shrimp (Litopenaeus vannamei) in Biofloc Systems - Hai-Hong Huang; Chao Cheng; Li-Li Guo; Wan-Sheng Zou; Yan-Ju Lei; Wei-Qi Kuang; Bo-Lan Zhou; Pin-Hong Yang; Chao-Yun Li (Fishes, 2025)
This study aimed to induce a shift in a bacterial community by adding substrate into a biofloc system to characterize this shift and estimate its benefits in improving water quality and aquatic animal growth. We compared the bacterial communities between two biofloc systems, either with (sB treatment) or without (nB treatment) the addition of substrate (elastic solid packing filler), and we also analyzed the effects of the shift on the water quality and growth performance of shrimp (Litopenaeus vannamei). Beta diversity analysis indicated that the bacterial communities in the two treatments were significantly different (Jaccard index 0.94 ± 0.01, pseudo-F = 3.96, p = 0.001). The addition of substrate showed significant positive effects on bacterial alpha diversity indices (Shannon, Heip, Pielou, and Simpson; p

One-pot remediation of binary organic-metal pollution: Efficient co-removal of BPA and Sb(III) by PMS-activated Fe-Mn@NC catalyst - Shuoshuo Mao; Jingjing Liu; Shanqi Liang; Lei Li; Pin Gao; Fang Li; Juan Zhou (Journal of Environmental Chemical Engineering, 2025)

Fungal mycelial pellet as a biosponge for bacterial immobilization: A novel biocarrier for synergistic adsorption-degradation of PAHs - Jia Jie Zou; Chaomeng Dai; Jiajun Hu; Wang Kai Tong; Hong Cheng Zhang; Min-tian Gao; Yalei Zhang; Zhi Li; Kah Hon Leong; Lang Zhou; Ken-Lin Chang; Swee Pin Yeap (Chemical Engineering Journal, 2025)

Dietary Supplementation with Multi-strain Probiotic Formulation (Bifidobacterium B8101, Lactobacillus L8603, Saccharomyces bayanus S9308, and Enterococcus SF9301), Betaine or their Combination Promotes Growth Performance Via Improving Intestinal Development in Broilers - Dan Hu; Xiaoting Wu; Pin Song; Manman Hou; Li’an Pan; Xiaoran Yang; Qinwei Sun; Yingdong Ni (Probiotics and Antimicrobial Proteins, 2025)

Novel insights into the effect of sTIM-3 on NLRP3 inflammasome via interacting with ASC - Xiaodi Zhang; Na Han; Ziqing Xu; Zheng Tong; Xiaolei Ren; Yang Sun; Chunyang Li; Xuetian Yue; Zhuanchang Wu; Xiaohong Liang; Chunhong Ma; Pin Wang; et al. (Inflammation Research, 2025)

Fluorescent visualization of endoplasmic reticulum stress induced by microplastic pollution via surge of intracellular reactive oxygen species - Le Yang; Xinchao Xia; Fan Li; Qiuhong Mo; Pin Shang; Junbin Li; Yi Li; Yibo Zhou; Zhihe Qing (Analytica Chimica Acta, 2025)

Peroxymonosulfate activation by iron-sulfur tailings doped with SiO2 for efficient degradation of tetracycline - Chen-Chen Yin; Chun Cheng; Peng-Yu Zhang; Zheng-Yuan Zhang; Ying Qin; Li-Pin Xue; Yu-Qi Feng; Bai Sun; Shu-guang Zhu (Environmental Science and Pollution Research, 2025)

Investigation of the ecological roles of the plastisphere microbiome in metal-contaminated river sediments: elucidation of their metabolic versatilities for plastics mineralization and metal resistance - Tianle Kong; Xiaoxu Sun; Pin Gao; Wei Huang; Xiaojie Guan; Zhimin Xu; Baoqin Li; Weimin Sun (Water Research, 2025)

Dramatically suppressed climate signals in the Yellow River - Yonggui Yu; Rick J. Yang; Gang Wang; Jaap H. Nienhuis; Xianyao Chen; James T. Liu; Marcel van der Perk; Rens van Beek; Xuefa Shi; Shuqing Qiao; Zhi Li; Jay Lee; et al. (Global and Planetary Change, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Complement factor D of Paralichthys olivaceus in serum enhances C3 deposition to activate complement against bacterial infection - Heng Liu; Xiao-yan Jin; Xue-pin Han; Yin Liu; Feng Zhang; Mo-fei Li (Fish & Shellfish Immunology, 2025)

Electroactive biofilm enhances synergistic degradation of sulfamethoxazole and roxarsone in actual livestock wastewater: extracellular electron transfer drives metabolic network remodeling - Pin Peng; Xinyu Yan; Lixiang Chen; Xiang Li; Huiying Yang; Yijing Miao; Feng Zhao (Environmental Research, 2025)

A novel sludge dewatering conditioner of chitin derivatives from waste black soldier fly puparia: Efficacy, key factors, and mechanisms - Junfeng Zhang; Yalin Yu; Wenhao Li; Pin Zhou; Nanwen Zhu; Shouqiang Huang; Amin Mojiri; Dongdong Ge (Process Safety and Environmental Protection, 2025)

Efficient activation of percarbonate by metal-free carbonylated activated carbon for green groundwater remediation: Performance, mechanism, applicability, and environmental implications - Jun Bo Zhang; Yi Yang; Chaomeng Dai; Jixiang Li; Yucang Liang; Jiajun Hu; Min-tian Gao; Xueji You; Xu Jiang; Shunyang Li; Xihua Wang; Zhi Li; et al. (Journal of Hazardous Materials, 2025)

Continuous cell lines from kidney and spleen of Japanese eel, Anguilla japonica, with capacity for antiviral immune response - Xiaoling Zhou; Dongli Li; Yanting Chen; Pin Nie; Bei Huang; Wenshu Huang (Fish & Shellfish Immunology, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

S-vacancy-rich MoS2 for enhanced BPA degradation involved peroxymonosulfate activation: sustainable transformation of toxic V(V) into a homogeneous catalyic system - Jingjing Liu; Shanqi Liang; Ting Xiang; Lei Li; Pin Gao; Juan Zhou (Journal of Water Process Engineering, 2025)

Tailoring lignocellulose-derived biochar for peroxymonosulfate-based catalytic environments: Optimizing active sites, revealing activation mechanisms, and advancing groundwater remediation applications - Jun Bo Zhang; Chaomeng Dai; Jiajun Hu; Jixiang Li; Min-tian Gao; Yeap Swee Pin; Kah Hon Leong; Ken-Lin Chang; Xing Song Xu; Xu Jiang (Journal of Hazardous Materials, 2025)

Innovative municipal sludge dewatering: High efficiency and high-dryness through the synergistic effect of MoS2 piezoelectric catalysis and electro-dewatering - Binqi Rao; Yulin Li; Zhuo Zeng; Yin Duan; Yan Zhang; Fang Zhou; Weilun Ren; Pin Zhou; Xilong Lu; Quanfa Zhou; Peng Xu (Journal of Environmental Management, 2025)

Variations in the leaf economics spectrum, anatomical, ultrastructural, and stomatal traits of five tree species in the urban-rural air pollution environment - Xiangru Yan; Pin Li; Xianjie Wu; Jiahui Wang; Zejin Wang; Jingliang Xu; Xiaofan Hou; Dayong Fan; Zhengbing Yan; Enzai Du (Journal of Environmental Sciences, 2025)

Performance and mechanism investigation of CO2 capture by novel ternary MEA/tertiary amine/sulfolane biphasic solvents - Guangjie Chen; Guangying Chen; Liuyi Yin; Fei Li; Li Sze Lai; Wee Horng Tay; Swee Pin Yeap; Lin Jin (International Journal of Greenhouse Gas Control, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

Aging of textile-based microfibers in both air and water environments - Shuyu Ma; Xiaopeng Min; Lin Xu; Xiaolong Jiang; Yanan Liu; Pin Gao; Peng Ji; Hyunjung Kim; Li Cai (Water Research, 2025)

Multi-hazard fragility analysis of cross-sea cable-stayed bridges cable bent tower under seismic-wind combined action - Yan Liang; Yu-zhen Kong; Li Yan; Zheng-hao Zhao; Pin-wu Guan (Soil Dynamics and Earthquake Engineering, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

In vivo molecular imaging of drug resistance in neuroblastoma using APE1 cyclically cleaved and miR-514a self-recycled programmable allosteric DNA nanomachine - Wancun Zhang; Zhenzhen Tian; Pin Zhang; Lifeng Li; Zhidan Yu; Meng Sun; Kangbo Liu; Ligong Hou; Jie Zhang; Mengxin Zhang; Xianwei Zhang (Chemical Engineering Journal, 2025)

Spatial-temporal projections of population exposure to extreme heat in China under different emission and population scenarios - Chenghua Shen; Yue Sheng; Yao Li; Pin Wang (Natural Hazards, 2025)

Upregulation of circRNA_0002286 protects against brain ischemia/reperfusion injury after remote ischemic postconditioning via microRNA-124-3p/VLCAD axis - Chun-Yan Li; Wei Ma; Jin-Wei Yang; Wei Liu; Kuang-Pin Liu; Xiao-Hua Weng; Shou-Rui Niu; Shen Li; Jian-Hui Guo; Li-Yan Li (Journal of Molecular Histology, 2025)

Deciphering the miRNA–mRNA Interaction Network Regulating Aging Skeletal Muscle in Various Exercise Regimens through Comprehensive Bioinformatics Analysis - Zhi Yu; Pin-Shi Ni; Zhuang-Zhi Wang; Zheng-Yang Zhao; Bao-Yi Chen; Zhen-En Zhang; Fang-Hui Li (Cell Biochemistry and Biophysics, 2025)

Quantitative analysis of anthocyanins and flavonoids in purple and green leaves of Eleutherococcus senticosus by UPLC-MS/MS techniques - Mei Hua; Meng Meng; Yu-pin Fu; Yun-qin Li (Natural Product Research, 2025)

Contributions of urbanization and population growth to changes in urban flood exposure in recent decades - Ziyi Tang; Pin Wang; Yao Li; Chaohui Chen; Yihan Lou; Tangao Hu (Sustainable Cities and Society, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

Genome-wide identification, expression analysis and transcriptional regulation of major histocompatibility complex class I genes in mandarin fish Siniperca chuatsi - Jing Hou; Min Chang Li; Lu Qi; Wei Hao; Lan Hao Liu; Zhen Gan; Bei Huang; Wen Shu Huang; Li Wang; Li Li; Shan Nan Chen; Pin Nie (Aquaculture, 2025)

Estimating basin-scale heterogeneous hydraulic diffusivity fields based on signal decomposition and river stage tomography - Bo-Tsen Wang; Yu-Li Wang; Chia-Hao Chang; Chin-Tsai Hsiao; Jordi Mahardika Puntu; Ping-Yu Chang; Jui-Pin Tsai (Journal of Hydrology, 2025)

Analyzing the effects of data splitting and covariate shift on machine learning based streamflow prediction in ungauged basins - Pin-Ching Li; Sayan Dey; Venkatesh Merwade (Journal of Hydrology, 2025)

Complete solidification of landfill concentrated leachate using a minimal dosage of mayenite and its reutilization for carbonyl sulfide degradation - Pin Zhou; Xin Li; Dongdong Ge; Nanwen Zhu; Yun Gu; Binglong Zhu; Shouqiang Huang (Journal of Hazardous Materials, 2025)

The mechanism of perilla oil in regulating lipid metabolism - Jiawei Xia; Yi Wang; Xin Li; Li Liu; Pin Zhang; Wendong Dai; Peng Luo; Guoze Wang; Yanhong Li (Food Chemistry, 2025)

Effect-directed analysis of the overlooked Ralstonia insidiosa induced Listeria monocytogenes aggregation under nutrient stress - Xifeng Zuo; Pin Chen; Zhe Liu; Qingyan Pan; Keying Li; Si Cheng; Ailing Guo (Food Bioscience, 2025)

Transcriptome analysis of head kidney and liver in grass carp (Ctenopharyngodon idella) symptomatically or asymptomatically infected with Flavobacterium columnare - Yong Jin; Nan Li; Shan Nan Chen; Yi Shan Lu; Zhen Gan; Pin Nie (Fish & Shellfish Immunology, 2025)

Structure identification and biological activity of a novel sulfated glycosaminoglycan-like polysaccharide from Sepia recurvirostra ink - Nanqi Cheng; Na Gao; Pin Wang; Yujun Ma; Pengfei Li; Xiaolu Wu; Jiaying Sun; Yulan Dai; Jinhua Zhao (Carbohydrate Polymers, 2025)

Recent progress in optimization of RANS turbulence models for accurate urban airflow and contaminant dispersion simulations - Sumei Liu; Longhui Xu; Bingqian Chen; Zhipeng Deng; Pin Li; Runmin Zhao; Qingyan Chen (Sustainable Cities and Society, 2025)

Immune response to polystyrene microplastics: Regulation of inflammatory response via the ROS-driven NF-κB pathway in zebrafish (Danio rerio) - Jincheng Pei; Shannan Chen; Qingxia Ke; Anning Pang; Mengmeng Niu; Nan Li; Jiayi Li; Zhi Wang; Hongjuan Wu; Pin Nie (Aquatic Toxicology, 2025)

Cardiovascular dysfunction and altered lysosomal signaling in a murine model of acid sphingomyelinase deficiency - Yun-Ting Wang; Alexandra K. Moura; Rui Zuo; Kiana Roudbari; Jenny Z. Hu; Saher A. Khan; Zhengchao Wang; Yangping Shentu; Mi Wang; Pin-Lan Li; Jiukuan Hao; Yang Zhang; et al. (Journal of Molecular Medicine, 2025)

Morphology, phylogeny, and toxicity of three Gambierdiscus species from the South China Sea, including a coral-killing bloom of G. carpenteri in reef tanks - Zhaohe Luo; Xiangyuan Lin; Xiaowan Liu; Kieng Soon Hii; Haiyan Li; Yan Li; Xinya Xu; Jiaguang Xiao; Hala F. Mohamed; Xinqing Zheng; Li Zhang; Po Teen Lim; et al. (Marine Environmental Research, 2025)

Spatial-confined CuCo bimetallic nanoparticles in nitrogen-doped carbon flowers enable low-input/input-free electrocatalytic hydrogen production - Fenghua Ge; Mengjiao Guo; Xu Dong; Fengcai Lei; Junfeng Xie; Qikun Zhang; Zhihua Li; Qian Wang; Pin Hao (Journal of Environmental Chemical Engineering, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Thermal-fluid coupled fracture behavior of fissured granite in a 3D crystal model - Heng Li; Sheng-Qi Yang; Bo-Wen Sun; Zhen Yang; Zhi-Jin Dong; Pin-Qiang Mo (Engineering Geology, 2025)

Sacrificial reduction effects derived inorganic-rich hybrid solid electrolyte interfaces for long-term and high reversibility aqueous zinc-ion batteries - Yu Chen; Jiahong Fan; Qian Li; Pin Yi; Houfu Tu; Dedong Shan; Wentao Wang; Shulin Zhao; Yang Zhang; Yuping Wu; Yuhui Chen; Dengji Xiao (Chemical Engineering Journal, 2025)

Impact of emerging technologies on corporate social responsibility in mining industry - Muhammad Haroon; Mirzat Ullah; Zhanqiang Li; Shuo Zhu; Judong Wang; Chu-Pin (Eugune) Hsueh (Resources Policy, 2025)

Microplastic types dominate the effects of bismuth oxide semi-conductor nanoparticles on their transport in saturated quartz sand - Lin Xu; Shaoyan Lv; Quanyuan Chen; Pin Gao; Genyao Gu; Yongxia Wang; Xiaopeng Min; Hyunjung Kim; Li Cai (Journal of Hazardous Materials, 2025)

Oligosaccharide-assisted resolution of holothurian fucosylated chondroitin sulfate for fine structure and P-selectin inhibition - Ying Pan; Huifang Sun; Xi Gu; Sujuan Li; Shengtao Yang; Liang Zhang; Hui Mao; Pin Wang; Shasha Yang; Ronghua Yin; Zhili Zuo; Jinhua Zhao (Carbohydrate Polymers, 2025)

Dry solidification of chloride salts and heavy metals in waste incineration fly ash by mayenite - Xin Li; Dongdong Ge; Nanwen Zhu; Yukai Zong; Shi Cheng; Pin Zhou; Min Jiang; Yun Gu; Shouqiang Huang (Waste Management, 2025)

A novel application of slow-release fertilizers in fertilizer-drawn forward osmosis for real domestic wastewater treatment - Chenchen Li; Pin Zhao; Zunaira Habib; Weilong Song; Xinhua Wang (Journal of Water Process Engineering, 2025)

Temporal bloom dynamics of the marine dinoflagellate Tripos furca in the Penang Strait - Nur Fatihah Mohd Azmi; Kieng Soon Hii; Minlu Liu; Siti Nursyuhada Baharudin; Nur Syazwani Kassim; Li Keat Lee; Monaliza Mohd Din; Nurin I. Mustapa; Roziawati Mohd Razali; Haifeng Gu; Chui Pin Leaw; Po Teen Lim (Harmful Algae, 2025)

Molecular diversity of benthic harmful dinoflagellates on a tropical reef: Comparing natural and artificial substrate sampling methods using DNA metabarcoding and morphological analysis - Nur Syazwani Kassim; Li Keat Lee; Kieng Soon Hii; Nur Fatihah Mohd Azmi; Siti Nursyuhada Baharudin; Minlu Liu; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Harmful Algae, 2025)

A Finite Element Analysis Comparing an Additive Manufacturing Lattice-Structured PEEK Implant to a Commercial Ball-and-Socket Design for Cervical Total Disc Replacement - Ming-Kai Hsieh; Fu-Cheng Kao; Yun-Da Li; De-Mei Lee; Hui Jin; Ching-Lung Tai; Tsung-Ting Tsai; Po-Liang Lai; Weng-Pin Chen (Journal of Medical and Biological Engineering, 2025)
Purpose Cervical total disc replacement (TDR) is commonly performed to treat degenerative cervical spondylosis, but it often faces challenges such as implant wear and migration. This study aimed to develop and evaluate a novel 3D-printed TDR featuring a titanium endplate and a lattice-structured poly-ether-ether-ketone (PEEK) design. The primary objective was to replicate the natural motion of the cervical disc while addressing complications associated with conventional TDRs. Methods The novel implant was created using additive manufacturing techniques, incorporating three lattice-structured PEEK designs (Cross, Octet, and Ventiles) for the nucleus pulposus and annulus fibrosus components. A finite element analysis was conducted to compare the biomechanical performance of the novel TDR with an intact cervical disc and a commercially available TDR (Baguera®C, Spineart SA, Geneva, Switzerland). Key parameters, including maximal von Mises stresses, range of motion, paths of the instantaneous center of rotation, and facet joint stresses, were evaluated under physiological loads (100 N follower load and 1.5 Nm pure moments). Results The novel 3D-printed TDR maintained structural integrity, with stresses remaining within the yield strength of PEEK. The biomechanical performance closely resembled that of an intact cervical disc, demonstrating similar ranges of motion, instantaneous center of rotation paths, and facet joint stress distributions. Conclusion The findings indicate that the innovative 3D-printed TDR may restore normal cervical spinal kinematics more effectively than existing commercial options, potentially reducing the risk of post-operative facet joint syndrome. Further experimental and clinical studies are recommended to validate these results.

Genetic patchiness of the endangered giant clam Tridacna maxima from Peninsular Malaysia - Li Keat Lee; Ya Yi Huang; Chaolun Allen Chen; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Po Teen Lim; Chui Pin Leaw (Coral Reefs, 2025)

Theory and field tests of innovative cut blasting method for rock roadway excavation - Chengxiao Li; Renshu Yang; Jinjing Zuo; Pin Xie (Tunnelling and Underground Space Technology, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Comparison of UV based advanced oxidation processes (UV/H2O2, UV/NaClO, and UV/Na2S2O8) for inactivating Uronema marinum in marine water - Xuan Chen; Pin Gan; Kunling Huang; Fangyu Liang; Tianhao Wu; Xudong Li; Yuanyuan Zhang (Journal of Water Process Engineering, 2025)

A “two birds one stone” strategy for self-healing marine coatings with antifouling and anticorrosion properties - Yong-Yin Cui; Tian-Cheng Chen; Jia-Ming Zhai; Ying Liu; Ye-Pin Gu; Hui-Jing Li; Yan-Chao Wu (Chemical Engineering Journal, 2025)

Ordered self-assembled monolayer improved the buried interface of wide bandgap perovskite for efficient and stable semi-transparent solar cells - Peiran Hou; Shenghan Hu; Yuxi Zhang; Junye Pan; Min Hu; Jiahui Chen; Bingxin Duan; Li Wan; Pin Lv; Yanqing Zhu; Shengqiang Xiao; Yi-Bing Cheng; et al. (Chemical Engineering Journal, 2025)

Unlocking anaerobic digestion potential via extracellular electron transfer by exogenous materials: Current status and perspectives - Xinyu Yan; Pin Peng; Xiang Li; Xudong Zhou; Lixiang Chen; Feng Zhao (Bioresource Technology, 2025)

Evaluation and mitigation of potentially toxic elements contamination in mangrove ecosystem: Insights into phytoremediation and microbial perspective - Gobinda Dey; Jyoti Prakash Maity; Pritam Banerjee; Raju Kumar Sharma; Koyeli Das; Gopalakrishnan Gnanachandrasamy; Chin-Wen Wang; Pin-Yun Lin; Shan-Li Wang; Chien-Yen Chen (Marine Pollution Bulletin, 2024)

Research on the optimal pick-up heights and their control strategy for the hydraulic double-row jet collector of the manganese nodule miner - Pin-Jian Wang; Li Li; Dong-Chao Xie; Mi-Qian Fan; Jia-Bin Wu (Ocean Engineering, 2024)

Enhancing degradation of antibiotic-combined pollutants by a hybrid system containing advanced oxidation and microbial treatment, a review - Pin Peng; Xinyu Yan; Xudong Zhou; Lixiang Chen; Xiang Li; Yijing Miao; Feng Zhao (Journal of Hazardous Materials, 2024)

Inhibitory effects of cold plasma-activated water on the generation of advanced glycation end products and methylimidazoles in cookies and mechanistic evaluation using electron paramagnetic resonance - Chenxia Zhang; Jian Zhang; Tiantian Huang; Pin Jiang; Xuejiao Qie; Lan Mo; Maiquan Li; Aihua Lou; Qingwu Shen; Jie Luo; Shuai Wang; Yi XueC; et al. (Food Chemistry, 2024)

Projected population exposure to precipitation extremes in China by the end of the twenty-first century: trends, change points, and spatial variability - Yue Sheng; Chenghua Shen; Yao Li; Pin Wang; Tangao Hu (Regional Environmental Change, 2024)

Sporelings and growth of the marine red alga, Gelidium elegans (Gelidiaceae), from Northern Taiwan - Showe-Mei Lin; Shih-Jhe Chen; Pin-Yu Huang; Li-Chia Liu; Yu-Shan Chiou (Journal of Applied Phycology, 2024)

Methylobacterium nigriterrae sp. nov., isolated from black soil - Le-Bin Chen; Yu-Ting OuYang; Lan Liu; Pin-Jiao Jin; Rong-Rong Huang; Wen-Yi Pan; Ying Wang; Jia-Ying Xing; Ting-Ting She; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Prevalence of HLA-B*58:01 allele among Malay, Chinese and Indian ethnic patients with gout attending primary care clinics in Malaysia - Wei Leik Ng; Boon Pin Kee; Norita Hussein; Chirk Jenn Ng; Sheh Wen Kuan; Fatimah Zahrah Mohd Zaidan; Siti Umi Fairuz Azmi; Sue-Mian Then; Zhenli Kwan; Nadeem Qureshi; Jing Ran Lim; Li Ying Wong; et al. (Journal of Community Genetics, 2024)

Possible toxification mechanisms of acute and chronic pentachlorophenol to Montipora digitata: Limitation of energy supply and immunotoxicity - Lan Luo; Pengfei Xue; Xuan Chen; Pin Gan; Xiaoli Li; Kefu Yu; Yuanyuan Zhang (Science of The Total Environment, 2024)

Projecting urban flood risk through hydrodynamic modeling under shared socioeconomic pathways - Yihan Lou; Pin Wang; Yao Li; Yindong Zhang; Bin Xie; Tangao Hu (Journal of Environmental Management, 2024)

Emerging transition metal sulfide/MXene composites for the application of electrochemical energy storage - Xianghui Hu; Pin Ma; Zehao Zhang; Jian Wang; Cheng Li; Yee Sin Ang; Haibo Li; Hui Ying Yang (Chemical Engineering Journal, 2024)

Impact of polystyrene nanoplastics on apoptosis and inflammation in zebrafish larvae: Insights from reactive oxygen species perspective - Jincheng Pei; Shannan Chen; Li Li; Kailun Wang; Anning Pang; Mengmeng Niu; Xueyun Peng; Nan Li; Hongjuan Wu; Pin Nie (Science of The Total Environment, 2024)

Nanoplastics composite norfloxacin induced changes in conformation and function of lysozyme and differential effects of co-exposure contamination - Hengyu Song; Pin Jiang; Houquan Tang; Zaifeng Wang; Xuan Ge; Xiangxiang Li; Falin He; Shuqi Guo; Guang Tian; Yuntao Qi; Shaoyang Hu; Rutao Liu (Science of The Total Environment, 2024)

Laboratorial radiative shocks with multiple parameters and first quantifying verifications to core-collapse supernovae - Lu Zhang; Jianhua Zheng; Zhenghua Yang; Tianming Song; Shuai Zhang; Tong Liu; Yunfeng Wei; Longyu Kuang; Longfei Jing; Zhiwei Lin; Liling Li; Hang Li; et al. (Science Bulletin, 2024)

Structural characterization and hypoglycemic activity of Cordyceps sinensis polysaccharide (CSP-3) - Pin Gong; Yingying Ke; Xiaojuan Wang; Hui Long; Wenjuan Yang; Jing Wang; Nan Li; Yanni Zhao; Fuxin Chen; Yuxi Guo (Food Bioscience, 2024)

From raw microalgae to bioplastics: Conversion of Chlorella vulgaris starch granules into thermoplastic starch - A. Six; D. Dauvillée; C. Lancelon-Pin; A. Dimitriades-Lemaire; A. Compadre; C. Dubreuil; P. Alvarez; J.-F. Sassi; Y. Li-Beisson; J.-L. Putaux; N. Le Moigne; G. Fleury (Carbohydrate Polymers, 2024)

Effects of Attachment Design and Aligner Material on Mandibular Canine Distal Bodily Movement in Aligner Treatment - Pin-Yu Chen; Heng-Li Huang; Jian-Hong Yu; Jui-Ting Hsu (Journal of Medical and Biological Engineering, 2024)
Purpose Dental crowding is a result of a mismatch between tooth size and arch dimensions, which leads to malocclusion; treatment often involves premolar extraction before orthodontic alignment. Clear aligners are limited in their ability to achieve canine distal bodily movement, a common orthodontic maneuver. This study investigated the impacts of attachment design and aligner material on the efficacy of canine distal bodily movement. Methods A finite element analysis was conducted to examine the impact of various attachment designs and two aligner materials, thermoplastic polyurethanes/polycarbonate (TPU/PC) and polyethylene terephthalate glycol-modified (PETG), on mandibular canine distal bodily movement. The investigation focused on the biomechanical responses in the periodontal ligament (PDL) and surrounding alveolar bone. Results Attachment configuration exerted a strong influence on mandibular canine movement. Vertically oriented attachment pairs positioned mesially (mesial occlusal–mesial cervical) resulted in the most effective canine distal bodily movement, followed by a rectangular attachment. TPU/PC aligners induced slightly higher principal stresses in the PDL and von Mises stress and strain in the surrounding alveolar bone compared with PETG aligners; however, the difference was negligible, amounting to less than 6%. Conclusion Attachment design, specifically vertically oriented pairs positioned mesially (mesial occlusal–mesial cervical), was determined to be the crucial factor influencing the efficacy of canine distal bodily movement. The choice of aligner material (TPU/PC or PETG) has minimal impact on this orthodontic procedure.

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Exploring the transcription start sites and other genomic features facilitates the accurate identification and annotation of small RNAs across multiple stress conditions in Mycobacterium tuberculosis - Hong-Leong Cheah; Marimuthu Citartan; Li-Pin Lee; Siti Aminah Ahmed; Mohd Zaki Salleh; Lay Kek Teh; Thean-Hock Tang (Functional & Integrative Genomics, 2024)

MicroRNA dynamics in irisin-mediated signaling pathways within adipose tissue - Ming-Yun Ho; Kai-Pin Chiu; Ming-Lung Tsai; Jih-Kai Yeh; Yi-Chun Huang; Yan-Rong Li; Horng-Dar Wang; I-Chang Hsieh; Ming-Shien Wen; Chao-Yung Wang (Journal of Biosciences, 2024)

Ionic liquid coupled plasma promotes acetic acid production during anaerobic fermentation of waste activated sludge: Breaking the restrictions of low bioavailable substrates and altering the metabolic activities of anaerobes - Jinling He; Xinyuan Jiang; Qi Qiu; Andere Clement Miruka; Xianbao Xu; Ai Zhang; Xiang Li; Pin Gao; Yanan Liu (Water Research, 2024)

Vanishing giants: An assessment on the population status of giant clams across Malaysia - Li Keat Lee; Mei Lin Neo; Kieng Soon Hii; Haifeng Gu; Chaolun Allen Chen; Po Teen Lim; Chui Pin Leaw (Regional Studies in Marine Science, 2024)

Comparison of the inactivation of Uronema marinum in mariculture by UV/chlorine, UV/monochloramine, and UV/chlorine dioxide: Efficiency, mechanism and feasibility - Pin Gan; Xuan Chen; Yuanyuan Zhang; Xudong Li; Fangyu Liang; Tianhao Wu; Pengfei Xue; Kefu Yu (Journal of Water Process Engineering, 2024)

Wastewater-based epidemiology to monitor 68 NPS/conventional drug use in Taipei metropolitan area in Taiwan during and after COVID-19 pandemic - Te-Tien Ting; Pin-Chuan Chen; Ya-Chi Chang; Pin-Ju Chiang; Hsu-Cheng Li; Shih-Hsun Chen; Pei-Chieh Chen; Hai-Tien Chu; Ping-Yu Chuang; Yi-Hsin Liu; Pai-Shan Chen (Journal of Hazardous Materials, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Characterization and Genomic Analysis of Affinirhizobium gouqiense sp. nov. Isolated from Seawater of Gouqi Island Located in the East China Sea and Reclassification of Rhizobium lemnae to the Genus Affinirhizobium as Affinirhizobium lemnae comb. nov. - Min He; Gen Chen; Ke-Jing Li; Xing-Xing Tang; Xiao-Xiao Liu; Chang-Bin Ren; Hou-Hong Liu; Hai Luo; Sanjit Chandra Debnath; Pin-Mei Wang; Hai-Xin Chen; Dao-Qiong Zheng (Current Microbiology, 2024)

Drought stress impacts soil microbial nutrient limitation more strongly than O3 pollution - Pin Li; Yuqian Sun; Xiaofan Hou (Applied Soil Ecology, 2024)

Research on the Power Output of Different Floating Wind Farms Considering the Wake Effect - Jiaping Cui; Xianyou Wu; Pin Lyu; Tong Zhao; Quankun Li; Ruixian Ma; Yingming Liu (Journal of Marine Science and Engineering, 2024)
For floating wind turbines, one of the most interesting and challenging issues is that the movement of the rotor is strongly related to its floating platform, which results in corresponding variations in the wake characteristics of the turbine. Because the aerodynamic efficiency of the downstream turbines is affected by the wake characteristics, the power output will consequently vary depending on the different types of floating wind turbines and floating wind farms used. In this study, the rotor movement, wake characteristics, and corresponding wind farm power output are analyzed using a numerical method for three typical floating wind turbines: the semisubmersible type, spar buoy type, and tension leg platform type with a 5 MW configuration. A fixed-bottom monopile wind turbine is adopted as a benchmark. The simulation results show that of the three floating wind turbines, the rotor position and wake center are most dispersed in the case of the spar buoy type, and its wake also has the lowest impact on downstream wind turbines. Additionally, the power output of the corresponding spar buoy type wind farm is also the highest at different wind speeds, followed by the semisubmersible type, tension leg platform type, and then the fixed-bottom type. In particular, at low wind speeds, the wake effects differ significantly among the various types of wind turbines.

Omics analysis of ‘Shine Muscat’ grape grafted on different rootstocks in response to cadmium stress - Yafeng Gu; Xiaobin Fan; Ke Jiang; Pin Liu; Huiqing Chang; Okbagaber Andom; Jieshan Cheng; Zhaojun Li (Science of The Total Environment, 2024)

Wildfire-vegetation-climate-human interactions in the central Taiwan region during 17.3–2.0 cal kyr BP, inferred from sediments of Toushe Basin - Abdur Rahman; Yuan-Pin Chang; Hong-Chun Li; Ling-Ho Chung; Yu-Min Chou; Liang-Chi Wang (Quaternary Science Reviews, 2024)

In-situ converting CoO@Co/RGO into Co/Co(OH)2/RGO for improved dye-sensitized photocatalytic H2 evolution - Weiying Zhang; Pin Ai; Lewang Yuan; Shaoqin Peng; Yuexiang Li (Fuel, 2024)

Exosomes Derived from Irradiated-Prostate Cancer Cells Promote Cancer Progression - Chien‑Chih Ke; Chikondi Jassi; Chih-Hung Chuang; Chiung-Yuan Ko; Shu-Pin Huang; Shih-Hsun Kuo; Chia-Yang Li; Ya‑Ju Hsieh (Journal of Medical and Biological Engineering, 2024)

The adsorption of cerium on synthetic δ-MnO2: Implications for Ce uptake behavior of hydrogenetic and early diagenetic ferromanganese nodules from the Western Pacific - Yayue Tang; Dengfeng Li; Pete Hollings; Xiaoming Sun; Yongjia Liang; Rui Wang; Jinzhou Peng; Yu Fu; Pin Wang (Marine Geology, 2024)

Evaluating the impact and heterogeneity of China's OFDI on total-factor carbon emission performance in Belt and Road Initiative countries - Pin Li; Qi He; Jinsuo Zhang; Jing Xiong (Journal of Cleaner Production, 2024)

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

IRF11 synergizes with STAT1 and STAT2 to promote type I IFN production - Zhiyuan Jiao; Wenxing Li; Chao Xiang; DongLi Li; Wenshu Huang; Pin Nie; Bei Huang (Fish & Shellfish Immunology, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Fulvic acid-mediated efficient anaerobic digestion for kitchen wastewater: Electrochemical and biochemical mechanisms - Xinyu Yan; Pin Peng; Xudong Zhou; Xiang Li; Lixiang Chen; Feng Zhao (Water Research, 2024)

Climate-regulation of organic carbon export in erosive mountain settings: A case study from Taiwan since the last glacial maximum - Li-Wei Zheng; Robert G. Hilton; Yuan-Pin Chang; Rick J. Yang; Xiaodong Ding; Xufeng Zheng; Tsung-Yu Lee; Hsi-Jih Lu; Jung-Tai Lu; Yu-Shih Lin; James T. Liu; Shuh-Ji Kao (Quaternary Science Reviews, 2024)

Incorporating carbon quantum dots into phosphotungstic acid ionic liquid materials for enhanced catalytic oxidative desulfurization - Jun Xiong; Haoxue Huang; Mei Zhang; Pin Song; Hongping Li; Jun Di (Fuel, 2024)

Molecular cloning and functional analyses of C–C motif chemokine ligand 3 (CCL3) in mandarin fish Siniperca chuatsi - Xiao Liu; Jia Xiang Ji; An Ning Pang; Li Li; Pin Nie; Li Qiang Zhang; Ke Wei Zeng; Shan Nan Chen (Fish & Shellfish Immunology, 2024)

Porous carbon endows mayenite with high activity to achieve closed-loop removal of chloride ions from desulfurization wastewater - Munyaradzi Alexander Zengeya; Dongdong Ge; Xin Li; Nanwen Zhu; Pin Zhou; Pengfei Xie; Shouqiang Huang (Chemical Engineering Journal, 2024)

MYPT1SMKO Mice Function as a Novel Spontaneous Age- and Hypertension-Dependent Animal Model of CSVD - Jian Chen; Cheng-Gang Li; Li-Xuan Yang; Yi Qian; Li-Wen Zhu; Pin-Yi Liu; Xiang Cao; Ye Wang; Min-Sheng Zhu; Yun Xu (Translational Stroke Research, 2024)

Red light induces starch accumulation in Chlorella vulgaris without affecting photosynthesis efficiency, unlike abiotic stress - A. Six; A. Dimitriades-Lemaire; C. Lancelon-Pin; J.-L. Putaux; D. Dauvillée; D. Petroutsos; P. Alvarez Diaz; J.-F. Sassi; Y. Li-Beisson; G. Fleury (Algal Research, 2024)

Co-pyrolysis of sewage sludge and phosphate tailings: Synergistically enhancing heavy metal immobilization and phosphorus availability - Ya Xiao; Tinggui Yan; Pin Yao; Weixue Xiang; Yunqi Wu; Jiang Li (Waste Management, 2024)

Enhanced cadmium absorption and tolerance of rice epiphytic microbes by iron oxide nanoparticles - Siduo Ding; Zhong Hu; Yuling Liu; Li Li; Yuhui Zeng; Doudou Jin; Anwei Chen; Jihai Shao; Pin Su; Si Luo (International Biodeterioration & Biodegradation, 2024)

Mo, N co-doped cobalt hydroxide nanosheets for highly selective methanol-to-formate electrocatalytic conversion - Yaoxin Wu; Lili Ban; Hanzhen Wang; Qian Yang; Yaao Li; Ke Lu; Yuxiang Li; Pin Cui; Jinfeng Yang; Dalei Chang; Dezheng Yang; Feng Yu; et al. (Chemical Engineering Journal, 2024)

Biogeochemistry of sedimentary organic matter in the Yongjiang River estuary in the southern part of Hangzhou Bay, China, since the Late Pleistocene - Dongqin Huang; Xiaolong Li; Zilong Li; Pei Sun Loh; Jianxiong Hu; Jianfang Chen; Yuan-Pin Chang; Chin-Wen Yang; Qin Gao (Journal of Oceanology and Limnology, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Numerical study on the structural performances of the collector of the polymetallic nodule mining vehicle under different operating modes - Pin-Jian Wang; Li Li; Jia-Bin Wu (Ocean Engineering, 2024)

Synergistic coupling of plasma with microbubbles for enhancing short-chain fatty acids production during sludge anaerobic fermentation: Mechanistic insights into reactive specie motivation and microbial community dynamics - Jinling He; Shuman Huang; Nan Jiang; Ai Zhang; Andere Clement Miruka; Yanan Liu; Xiang Li; Pin Gao; Gang Xue (Journal of Cleaner Production, 2024)

Sex differences in the benefit of tea consumption: A critical summation of the epidemiological evidence - Changhuai He; Pin Ye; Xuecheng Zhang; Yiqing Li; Qingping Li; Ping Lü; Chuanqi Cai; Xun Cai (Food Bioscience, 2024)

Endowing polymeric carbon nitride photocatalyst with CO2 activation sites by anchoring atomic cobalt cluster - Yaru Shang; Yijie Hou; Xun Cao; Hengjie Liu; Xiaoli Jin; Jiawei Liu; Chunshuang Yan; Yumin Qian; Li Song; Zeming Qi; Pin Song; Yansong Zhou; et al. (Chemical Engineering Journal, 2024)

Resource recovery of high value-added products from wastewater: Current status and prospects - Zihan Wei; Yan Qin; Xiang Li; Pin Gao (Bioresource Technology, 2024)

Microbial-mediated oxidative dissolution of orpiment and realgar in circumneutral aquatic environments - Xiaoxu Sun; Duanyi Huang; Yuqing Huang; Max Häggblom; Mohsen Soleimani; Jiayi Li; Zheng Chen; Zhenyu Chen; Pin Gao; Baoqin Li; Weimin Sun (Water Research, 2024)

Numerical investigation of the hydrodynamic characteristics of the polymetallic nodule miner considering the internal fluid field - Pin-Jian Wang; Li Li; Jia-Bin Wu (Ocean Engineering, 2024)

Valorization of coconut peat to develop a novel shape-stabilized phase change material for thermal energy storage - Pin Jin Ong; Si Hui Angela Goh; Yihao Leow; Suxi Wang; Pei Wang; Zibiao Li; Xuesong Yin; Beng Hoon Tan; Warintorn Thitsartarn; Jianwei Xu; Xian Jun Loh; Dan Kai; et al. (Journal of Cleaner Production, 2024)

The effect of lactic acid bacteria fermentation on physicochemical properties of starch from fermented proso millet flour - Tongze Zhang; Siqi Hong; Jia-Rong Zhang; Pin-He Liu; Siyi Li; Zixian Wen; Jianwei Xiao; Guirong Zhang; Olivier Habimana; Nagendra P. Shah; Zhongquan Sui; Harold Corke (Food Chemistry, 2024)

Exposure to pesticides and risk of colorectal cancer: A systematic review and meta-analysis - Pin-Peng Xie; Zhi-Qiang Zong; Jian-Chao Qiao; Zhuo-Yan Li; Cheng-Yang Hu (Environmental Pollution, 2024)

Economical-effective purification of brackish water through an integrated capacitive desalination & boron adsorption system - Liping Yang; Yixiang Li; Lu Guo; Pin Ma; Zhi Yi Leong; Jing Wang; Hui Ying Yang (Desalination, 2024)

Modification of grilles to improve the lavatory environment on an aircraft - Tengfei (Tim) Zhang; Pin Li; Chao-Hsin Lin; Feng Wang (Building and Environment, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

Acute hepatic and kidney injury after ingestion of Lepiota brunneoincarnata: Report of 2 cases - JiaJu Zhong; Pin Xu; HaiJiao Li; ChengYe Sun; Yun Tong; QunMei Yao; ChengMin Yu (Toxicon, 2024)

AaABCG20 transporter involved in cutin and wax secretion affects the initiation and development of glandular trichomes in Artemisia annua - Xueqing Fu; Han Zheng; Yuting Wang; Hang Liu; Pin Liu; Ling Li; Jingya Zhao; Xiaofen Sun; Kexuan Tang (Plant Science, 2024)

Contributions of climate change and urbanization to urban flood hazard changes in China's 293 major cities since 1980 - Ziyi Tang; Pin Wang; Yao Li; Yue Sheng; Ben Wang; Nataliia Popovych; Tangao Hu (Journal of Environmental Management, 2024)

Management of the designed risk level of urban drainage system in the future: Evidence from haining city, China - Yihan Lou; Pin Wang; Yao Li; Luoyang Wang; Chaohui Chen; Jiahui Li; Tangao Hu (Journal of Environmental Management, 2024)

Numerical studies of gasoline direct-injection sprays (ECN Spray G) under early- and late-injection conditions using Large Eddy Simulation and droplets-statistics-based Eulerian–Lagrangian framework - Hao-Pin Lien; Yongxiang Li; Andrea Pati; Amsini Sadiki; Christian Hasse (Fuel, 2024)

Simultaneous removal of organic micropollutants and metals from water by a multifunctional β-cyclodextrin polymer-supported-polyaniline composite - Pin Wang; Guangyu An; Peter Jarvis; Wen Liu; Shunke Ding; Ruixin Qu; Zhanghan Li; Cheng Ye; Wenhai Chu (Chemical Engineering Journal, 2024)

Bifunctional drug delivery system with carbonic anhydrase IX targeting and glutathione-responsivity driven by host-guest amphiphiles for effective tumor therapy - Jiawei Zhou; Yamin Li; Lutao Wang; Pin Lv; Miao Chen; Feijian Xiao; Tian Si; Jun Tao; Bo Yang (Carbohydrate Polymers, 2024)

Intra-subject enveloped multilayer fuzzy sample compression for speech diagnosis of Parkinson's disease - Yiwen Wang; Fan Li; Xiaoheng Zhang; Pin Wang; Yongming Li; Yanling Zhang (Medical & Biological Engineering & Computing, 2024)

Exposure to pentachlorophenol destructs the symbiotic relationship between zooxanthellae and host and induces pathema in coral Porites lutea - Yuanyuan Zhang; Lan Luo; Pin Gan; Xuan Chen; Xiaoli Li; Yan Pang; Xiaopeng Yu; Kefu Yu (Science of The Total Environment, 2024)

V-ATPase E mediates Cry2Ab binding and toxicity in Helicoverpa armigera - Yuge Zhao; Pin Li; Xue Yao; Yuepu Li; Yu Tian; Guiying Xie; Zhongyuan Deng; Shuxia Xu; Jizhen Wei; Xianchun Li; Shiheng An (Pesticide Biochemistry and Physiology, 2024)

Activation of peroxymonosulfate by sewage sludge-derived biochar to promote short-chain fatty acid production during sludge anaerobic fermentation - Jinling He; Qingchen Wu; Nan Jiang; Ai Zhang; Lin Wang; Xiang Li; Gang Xue; Hong Chen; Pin Gao (Chemical Engineering Journal, 2024)

Coded-Aperture imaging based on random code and Backpropagation neural network - Zeyu Wang; Chao Wang; Pin Gong; Liansheng Li; Zhimeng Hu; Yongqiang Shi; Xiaolei Shen; Cheng Zhou; Xiaoxiang Zhu; Xiaobin Tang (Annals of Nuclear Energy, 2024)

Oxidative stress responses of the scleractinian coral Acropora digitifera from the tropical Bidong Island, Malaysia - focus on protein thiol groups' detection - Muhammad Arif Samshuri; Che Din Mohd Safuan; Siti Nurtahirah Jaafar; Chui Pin Leaw; Li Keat Lee; Mathinee Yucharoen; Zainudin Bachok (Journal of Experimental Marine Biology and Ecology, 2023)

Exploration of the Catalytic Cycle Dynamics of Vigna Radiata H+–Translocating Pyrophosphatases Through Hydrogen–Deuterium Exchange Mass Spectrometry - Li-Kun Huang; Yi-Cyuan Huang; Pin-Chuan Chen; Ching-Hung Lee; Shih-Ming Lin; Yuan-Hao Howard Hsu; Rong-Long Pan (The Journal of Membrane Biology, 2023)

Association of co-exposure to metal(loid)s during pregnancy with birth outcomes in the Tibetan plateau - Lei Zhao; Tiemei Li; Haijing Wang; Yue-Mei Fan; Yuancan Xiao; Xuejun Wang; Shulin Wang; Pin Sun; Pinhua Wang; Zhaxi Jiangcuo; Li Tong; Liehong Wang; et al. (Chemosphere, 2023)

The impact of air pollution on respiratory diseases in an era of climate change: A review of the current evidence - Huan Minh Tran; Feng-Jen Tsai; Yueh-Lun Lee; Jer-Hwa Chang; Li-Te Chang; Ta-Yuan Chang; Kian Fan Chung; Han-Pin Kuo; Kang-Yun Lee; Kai-Jen Chuang; Hsiao-Chi Chuang (Science of The Total Environment, 2023)

Strategies analysis for improving SWAT model accuracy and representativeness of calibrated parameters in sediment simulation for various land use and climate conditions - Li-Chi Chiang; Pin-Chih Shih; Chih-Mei Lu; Bing-Chen Jhong (Journal of Hydrology, 2023)

Metal ion assistant transformation strategy to synthesize catechol-based metal–organic frameworks from Ti3C2T precursors - Weikang Wang; Yan Bai; Pin Yang; Shuai Yuan; Feiyang Li; Weiwei Zhao; Beibei Jin; Xuan Zhang; Shujuan Liu; Daqiang Yuan; Qiang Zhao (Science Bulletin, 2023)

Cationic segregation of Ca2Mn3O8 enabling high selectivity for fluoride ions through capacitive deionization - Wei Wang; Pin Ma; Haibo Li (Desalination, 2023)

TAT-PEP Alleviated Cognitive Impairment by Alleviating Neuronal Mitochondria Damage and Apoptosis After Cerebral Ischemic Reperfusion Injury - Pin Zhao; Jiapo Zhang; JianKe Kuai; Liya Li; Xuying Li; Namin Feng; Hailiang Du; Chen Li; Qiang Wang; Bin Deng (Molecular Neurobiology, 2023)
Paired immunoglobulin-like receptor B (PirB) was identified as a myelin-associated inhibitory protein (MAIP) receptor that plays a critical role in axonal regeneration, synaptic plasticity and neuronal survival after stroke. In our previous study, a transactivator of transcription-PirB extracellular peptide (TAT-PEP) was generated that can block the interactions between MAIs and PirB. We found that TAT-PEP treatment improved axonal regeneration, CST projection and long-term neurobehavioural recovery after stroke through its effects on PirB-mediated downstream signalling. However, the effect of TAT-PEP on the recovery of cognitive function and the survival of neurons also needs to be investigated. In this study, we investigated whether pirb RNAi could alleviate neuronal injury by inhibiting the expression of PirB following exposure to oxygen–glucose deprivation (OGD) in vitro. In addition, TAT-PEP treatment attenuated the volume of the brain infarct and promoted the recovery of neurobehavioural function and cognitive function. This study also found that TAT-PEP exerts neuroprotection by reducing neuronal degeneration and apoptosis after ischemia–reperfusion injury. In addition, TAT-PEP improved neuron survival and reduced lactate dehydrogenase (LDH) release in vitro. Results also showed that TAT-PEP reduced malondialdehyde (MDA) levels, increased superoxide dismutase (SOD) activity and reduced reactive oxygen species (ROS) accumulation in OGD-injured neurons. The possible mechanism was that TAT-PEP could contribute to the damage of neuronal mitochondria and affect the expression of cleaved caspase 3, Bax and Bcl-2. Our results suggest that PirB overexpression in neurons after ischaemic-reperfusion injury induces neuronal mitochondrial damage, oxidative stress and apoptosis. This study also suggests that TAT-PEP may be a potent neuroprotectant with therapeutic potential for stroke by reducing neuronal oxidative stress, mitochondrial damage, degeneration and apoptosis in ischemic stroke.

Long-term detraining reverses the improvement of lifelong exercise on skeletal muscle ferroptosis and inflammation in aging rats: fiber-type dependence of the Keap1/Nrf2 pathway - Zhuang-Zhi Wang; Hai-Chen Xu; Huan-Xia Zhou; Chen-Kai Zhang; Bo-Ming Li; Jia-Han He; Pin-Shi Ni; Xiao-Ming Yu; Yun-Qing Liu; Fang-Hui Li (Biogerontology, 2023)

The combined effects of North Atlantic Oscillation and Western Pacific teleconnection on winter temperature in Eastern Asia during 1980–2021 - Ziqun Zhang; Hongyan Cui; Baoxu Chen; Hong Cai; Pin Li (Acta Oceanologica Sinica, 2023)

Genesis of ferromanganese nodules associated with mud volcanoes in the southeastern Dongsha waters of the northern South China Sea: Implications for regional deep Mesozoic hydrocarbon prospects - Yunfan Zhang; Pengchun Li; Yongbin Jin; Xingjian Liu; Yanlin Wang; Pin Yan; Guangjian Zhong; Yunying Zhang (Marine and Petroleum Geology, 2023)

Monitoring terrestrial wildlife by combining hybridization capture and metabarcoding data from waterhole environmental DNA - Juan Li; Peter Seeber; Jan Axtner; Rachel Crouthers; Milou Groenenberg; Arnulf Koehncke; Alexandre Courtiol; Pin Chanratana; Alex D. Greenwood (Biological Conservation, 2023)

On constructing limits-of-acceptability in watershed hydrology using decision trees - Abhinav Gupta; Rao S. Govindaraju; Pin-Ching Li; Venkatesh Merwade (Advances in Water Resources, 2023)

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

Electrons of d-orbital (Mn) and p-orbital (N) enhance the photocatalytic degradation of antibiotics by biochar while maintaining biocompatibility: A combined chemical and biological analysis - Jinrui Dong; Pin Li; Xiaoyuan Ji; Yong Kang; Xue Yuan; Jingchun Tang; Boxiong Shen; Huajiang Dong; Honghong Lyu (Journal of Hazardous Materials, 2023)

Molecular cloning and functional analysis of polymeric immunoglobulin receptor, pIgR, gene in mandarin fish Siniperca chuatsi - Jia Xiang Ji; Lin Zhang; Li Li; Kai Lun Wang; Jing Hou; Lan Hao Liu; Bo Li; Bai Dong Zhang; Nan Li; Shan Nan Chen; Pin Nie (Fish & Shellfish Immunology, 2023)

Rational targeting of autophagy in colorectal cancer therapy: From molecular interactions to pharmacological compounds - Canhui Jin; Tianbao Wang; Yanhui Yang; Pin Zhou; Juncheng Li; Wenhao Wu; Xin Lv; Guoqing Ma; Aihong Wang (Environmental Research, 2023)

A Novel Approach to Three-Dimensional Inference and Modeling of Magma Conduits with Exploration Data: A Case Study from the Jinchuan Ni–Cu Sulfide Deposit, NW China - Xiancheng Mao; Pin Liu; Hao Deng; Zhankun Liu; Longjiao Li; Yushan Wang; Qixing Ai; Jianxin Liu (Natural Resources Research, 2023)

Effects of Bacillus strain added as initial indigenous species into the biofloc system rearing Litopenaeus vannamei juveniles on biofloc preformation, water quality and shrimp growth - Hai-Hong Huang; Chao-Yun Li; Yan-Ju Lei; Bo-Lan Zhou; Wei-Qi Kuang; Wan-Sheng Zou; Pin-Hong Yang (Aquaculture, 2023)

Future changes in urban drainage pressure caused by precipitation extremes in 285 cities across China based on CMIP6 models - Pin Wang; Yao Li; Jinjin Fan; Feng Kong; Dengrong Zhang; Tangao Hu (Sustainable Cities and Society, 2023)

Load identification of a 2.5 MW wind turbine tower using Kalman filtering techniques and BDS data - Da Wei; Dongsheng Li; Tao Jiang; Pin Lyu; Xiaofei Song (Engineering Structures, 2023)

Estimating divergent forest carbon stocks and sinks via a knife set approach - Shitephen Wang; Keito Kobayashi; Satoru Takanashi; Chiung-Pin Liu; Dian-Rong Li; San-Wen Chen; Yu-Ting Cheng; Kai Moriguchi; Masako Dannoura (Journal of Environmental Management, 2023)

Evolution of micro-damage and degradation of macro-mechanical properties of sandstone due to thermal effects - Pin Wang; Tubing Yin; Xibing Li; Heinz Konietzky (Bulletin of Engineering Geology and the Environment, 2023)

Cytotoxic triterpenoids from the roots of Bupleurum scorzonerifolium - Dan-Qi Li; Zi-Wei Zhao; Fan Jiang; Da Liu; Xiao-Jing Wu; Xue-Gui Liu; Pin-Yi Gao (Phytochemistry Letters, 2023)

Thiobacillus spp. and Anaeromyxobacter spp. mediate arsenite oxidation-dependent biological nitrogen fixation in two contrasting types of arsenic-contaminated soils - Yongbin Li; Lifang Guo; Rui Yang; Zhaohui Yang; Haihan Zhang; Qiqian Li; Zhiguo Cao; Xin Zhang; Pin Gao; Wenlong Gao; Geng Yan; Duanyi Huang; et al. (Journal of Hazardous Materials, 2023)

Occurrence, spatial distribution, and sources of PFASs in the water and sediment from lakes in the Tibetan Plateau - Yu Chen; Lijia Wei; Wei Luo; Ning Jiang; Yali Shi; Pin Zhao; Bila Ga; Zhiguo Pei; Yingming Li; Ruiqiang Yang; Qinghua Zhang (Journal of Hazardous Materials, 2023)

What factors contribute to the extent of decoupling economic growth and energy carbon emissions in China? - Pinjie Xie; Ningyu Gong; Feihu Sun; Pin Li; Xianyou Pan (Energy Policy, 2023)

Single-atom Mn anchored on N-doped graphene oxide for efficient adsorption-photocatalytic degradation of sulfanilamide in water: Electronic interaction and mineralization pathway - Honghong Lyu; Pin Li; Jingchun Tang; Weixin Zou; Pengfei Wang; Bin Gao; Lin Dong (Chemical Engineering Journal, 2023)

Research on the lightweight structural optimization design of the front collector of the polymetallic nodule miner - Pin-Jian Wang; Li Li; Jia-Bin Wu (Ocean Engineering, 2023)

Investigating relationships between landscape patterns and surface runoff from a spatial distribution and intensity perspective - Luoyang Wang; Hao Hou; Yao Li; Jing Pan; Pin Wang; Ben Wang; Jie Chen; Tangao Hu (Journal of Environmental Management, 2023)

Hypervalent potassium xanthate modified SnO2 for highly efficient perovskite solar modules - Pin Lv; Yufei Yang; Neng Li; Yuxi Zhang; Min Hu; Bo Huang; Yanqing Zhu; Yulong Wang; Junye Pan; Shifeng Wang; Bo Zhang; Fuzhi Huang; et al. (Chemical Engineering Journal, 2023)

Fabrication of a core-shell porphyrin-based magnetic covalent organic framework for effective extraction of PCPs in a wide polarity range - Tao Ning; Siyuan Di; Zihan Li; Haokun Zhang; Zhangdi Peng; Hucheng Yang; Pin Chen; Yue Bao; Yixin Zhai; Shukui Zhu (Analytica Chimica Acta, 2023)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Analyzing spatial variance of urban waterlogging disaster at multiple scales based on a hydrological and hydrodynamic model - Luoyang Wang; Yao Li; Hao Hou; Yan Chen; Jinjin Fan; Pin Wang; Tangao Hu (Natural Hazards, 2022)

Importance of surface charge of soot nanoparticles in determining inhalation toxicity in mice - Ta-Chih Hsiao; Chia-Li Han; Tzu-Ting Yang; Yueh-Lun Lee; Yu-Fang Shen; Yu-Teng Jheng; Chii-Hong Lee; Jer-Hwa Chang; Kian Fan Chung; Han-Pin Kuo; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Oceanobacillus saliphilus sp. nov., Isolated from Saline−Alkali Soil in Heilongjiang Province, China - Yu-Ting OuYang; Meng-Meng Li; Ai-Ping Lv; Pin-Jiao Jin; Lan Liu; Ze-Tao Liu; Jian-Yu Jiao; Wen-Jun Li; Li-Xiang Cao; Shuang Wang (Current Microbiology, 2022)

CDK1 promotes the proliferation of melanocytes in Rex rabbits - Yingying Dai; Shuaishuai Hu; Shaocheng Bai; Jiali Li; Naisu Yang; Pin Zhai; Bohao Zhao; Yang Chen; Xinsheng Wu (Genes & Genomics, 2022)

Bioactivity-guided isolation of compounds from Sophora flavescens with antibacterial activity against Acinetobacter baumannii - Pin Li; Wern Chern Chai; Zhan-Yi Wang; Kai-Jun Tang; Jin-Yao Chen; Henrietta Venter; Susan J. Semple; Lan Xiang (Natural Product Research, 2022)

Optimal Design of the Seepage Control for Xianglushan Diversion Tunnel Under High External Water Pressure - Zhen-jie Zhang; Chun-pin Zeng; Hu Li; Yang Gao; Liang Gong; Yu-xing Li; Hai-fang Liang; En-zhong Zhang (Geotechnical and Geological Engineering, 2022)

Effects of perfluorooctanoic acid (PFOA) on activated sludge microbial community under aerobic and anaerobic conditions - Duanyi Huang; Rui Xu; Xiaoxu Sun; Yongbin Li; Enzong Xiao; Zhimin Xu; Qi Wang; Pin Gao; Zhaohui Yang; Hanzhi Lin; Weimin Sun (Environmental Science and Pollution Research, 2022)

An Energy-Saving Position Control Strategy for Deep-Sea Valve-Controlled Hydraulic Cylinder Systems - Jia-Bin Wu; Li Li; Yong-Kang Yan; Pin-Jian Wang; Wei Wei (Journal of Marine Science and Engineering, 2022)
The valve-controlled hydraulic cylinder system (VCHCS) is commonly utilized in the underwater manipulator, which is the most important tool for subsea tasks. Hydraulic oil viscosity is very sensitive to pressure. Therefore, when working at different depths under different ambient pressures in the sea, the hydraulic oil viscosity and the pipeline pressure loss in the deep-sea VCHCS vary greatly, which seriously affects the energy efficiency of the system. In addition, the control accuracy of the deep-sea VCHCS is also influenced by changes in the hydraulic oil viscosity and the pipeline pressure loss. In order to realize energy-saving control, this research introduces a proportional relief valve and develops a variable pump pressure control strategy. At the same time, a variable gain proportional-integral-derivative (PID) algorithm is designed to achieve precise control. A co-simulation model of the deep-sea VCHCS is then established, and many simulation analyses are carried out. Compared with traditional PID control with a constant pump pressure, the proposed method presents advantages such as lower energy consumption, better control accuracy, better resistance to load impact, and accuracy consistency under different working depths. Among them, when working at 11 km depth in the sea, the proposed method is capable of saving energy by 36.5% for the multi-step movement, by 30% for the harmonic movement, and by 47% for the complex movement. The present work in this research provides a solution that can realize energy saving and precise control of the deep-sea VCHCS at the same time in the wide span of depth in the sea.

Working Performance of the Deep-Sea Valve-Controlled Hydraulic Cylinder System under Pressure-Dependent Viscosity Change and Hydrodynamic Effects - Jia-Bin Wu; Li Li; Xing-Long Zou; Pin-Jian Wang; Wei Wei (Journal of Marine Science and Engineering, 2022)
The valve-controlled hydraulic cylinder system (VCHCS) is commonly used for actuators such as manipulators in deep-sea equipment, whose working performance is crucial to subsea tasks. Affected by the ambient pressure introduced by the pressure compensator, the viscosity of the hydraulic oil increases significantly. On this basis, the viscosity changes further when flowing in the slender pipeline, making the pipeline pressure loss substantially increase and subsequently affecting the working performance of the deep-sea VCHCS. Aiming at this issue, a detailed nonlinear mathematical model of the deep-sea VCHCS is established, in which the viscosity-pressure characteristics of the hydraulic oil is considered to take the viscosity changes in the pipeline into account. Besides, the hydrodynamic effects are also included in the model. Then the corresponding numerical simulation model of the deep-sea VCHCS is established, and its working performance at different depths is simulated and analyzed. When the depth is 11km, the extension and retraction movements are delayed by 52.50% and 43.12% respectively. The root cause of the delay is then analyzed and discussed. Finally, the parameters that affect the working performance are studied, and suggestions to reduce or eliminate the delay phenomenon are given. The results can provide theoretical support for the performance optimization of the deep-sea VCHCS.

Metabolic potentials of members of the class Acidobacteriia in metal‐contaminated soils revealed by metagenomic analysis - Rui Xu; Xiaoxu Sun; Max M. Häggblom; Yiran Dong; Miaomiao Zhang; Zhaohui Yang; Enzong Xiao; Tangfu Xiao; Pin Gao; Baoqin Li; Weimin Sun (Environmental Microbiology, 2022)
Summary The relative abundance of Acidobacteriia correlated positively with the concentrations of arsenic (As), mercury (Hg), chromium (Cr), copper (Cu) and other metals, suggesting their adaptation of the metal‐rich environments. Metagenomic binning reconstructed 29 high‐quality metagenome‐assembled genomes (MAGs) associated with Acidobacteriia , providing an opportunity to study their metabolic potentials. These MAGs contained genes to transform As, Hg and Cr through oxidation, reduction, efflux and demethylation, suggesting the potential of Acidobacteriia to transform such metal(loid)s. Additionally, genes associated with alleviation of acidic and metal stress were also detected in these MAGs. Acidobacteriia may have the capabilities to resist or transform metal(loid)s in acidic metal‐contaminated sites. Moreover, these genes encoding metal transformation could be also identified in the Acidobacteriia ‐associated MAGs from five additional metal‐contaminated sites across Southwest China, as well as Acidobacteriia ‐associated reference genomes from the NCBI database, suggesting that the capability of metal transformation may be widespread among Acidobacteriia members. This discovery provides an understanding of metabolic potentials of the Acidobacteriia in acidic metal‐rich sites.

Alteribacter salitolerans sp. nov., isolated from a saline-alkaline soil - Shuang Wang; Lei Sun; Manik Prabhu Narsing Rao; Guo-Hong Liu; Pin-Jiao Jin; Zhou-Yan Dong; Zheng-Han Lian; Xiao-Yu Hao; Ming-Yi Zhang; Wen-Jun Li (Archives of Microbiology, 2022)

Citric acid and AMF inoculation combination–assisted phytoextraction of vanadium (V) by Medicago sativa in V mining contaminated soil - Lang Qiu; Wenlong Gao; Zhigang Wang; Baoqin Li; Weimin Sun; Pin Gao; Xiaoxu Sun; Benru Song; Yanxu Zhang; Tianle Kong; Hanzhi Lin (Environmental Science and Pollution Research, 2021)

Acute temperature changes induce an oxidative stress response in kidney cells of grass carp Ctenopharyngodon idellus - Pin Ma; Xiaoyan Yin; Dapeng Li; Li Li; Rong Tang (Fisheries Science, 2021)

Structure and variation of root-associated bacterial communities of Cyperus rotundus L. in the contaminated soils around Pb/Zn mine sites - Pin Gao; Benru Song; Rui Xu; Xiaoxu Sun; Hanzhi Lin; Fuqing Xu; Baoqin Li; Weimin Sun (Environmental Science and Pollution Research, 2021)

3D Step-by-step inversion strategy for audio magnetotellurics data based on unstructured mesh - San Cheng; Zhi-Yong Zhang; Feng Zhou; Man Li; Hui Chen; Fu-Sheng Shi; Lin-Pin Huang; Yong Li (Applied Geophysics, 2021)

Dietary selenium promotes the growth performance through growth hormone–insulin-like growth factor and hypothalamic–pituitary–thyroid axes in grass carp (Ctenopharyngodon idella) - Pin Ma; Zhenyi Hu; Li Li; Dapeng Li; Rong Tang (Fish Physiology and Biochemistry, 2021)

Genome sequencing and comparative genome analysis of 6 hypervirulent Klebsiella pneumoniae strains isolated in China - Ling Du; Jiaxue Zhang; Pin Liu; Xuan Li; Kewen Su; Lingyue Yuan; Zhongshuang Zhang; Dan Peng; Yingli Li; Jingfu Qiu (Archives of Microbiology, 2021)

SAA1 regulates pro-labour mediators in term labour by activating YAP pathway - Yanmin Jiang; Li Pin; Weiqun Shi; Qian Huang; Lele Wang; Huishu Liu (Molecular and Cellular Biochemistry, 2021)

Strong in vitro and in vivo cytotoxic effects of two platinum(II) complexes with cryptolepine derivatives - Li-Qin Qin; Zu-Zhuang Wei; Lin Yang; Qi-Pin Qin; Jia-Jing Zeng; Ming-Xiong Tan; Hong Liang (Medicinal Chemistry Research, 2021)

Impact of the Benguela coastal low-level jet on the southeast tropical Atlantic SST bias in a regional ocean model - Jaison Kurian; Pin Li; Ping Chang; Christina M. Patricola-DiRosario; Justin Small (Climate Dynamics, 2021)

Multimodal Image Analysis of Sexual Dimorphism in Developing Childhood Brain - Xiujun Yang; Aojie Li; Lihong Li; Tingting Li; Pin Li; Manhua Liu (Brain Topography, 2021)

The Roles of Epinephelus coioides miR-122 in SGIV Infection and Replication - Hong-Yan Sun; Yu-Ling Su; Pin-Hong Li; Jia-Yang He; He-Jia Chen; Gang Wang; Shao-Wen Wang; Xiao-Hong Huang; You-Hua Huang; Qi-Wei Qin (Marine Biotechnology, 2021)
In mammals, mature miR-122 is 22 nucleotides long and can be involved in regulating a variety of physiological and biological pathways. In this study, the expression profile and effects of grouper Epinephelus coioides miR-122 response to Singapore grouper iridovirus (SGIV) infection were investigated. The sequences of mature microRNAs (miRNAs) from different organisms are highly conserved, and miR-122 from E. coioides exhibits high similarity to that from mammals and other fish. The expression of miR-122 was up-regulated during SGIV infection. Up-regulation of miR-122 could significantly enhance the cytopathic effects (CPE) induced by SGIV, the transcription levels of viral genes (MCP, VP19, LITAF and ICP18), and viral replication; reduce the expression of inflammatory factors (TNF-a, IL-6, and IL-8), and the activity of AP-1 and NF-κB, and miR-122 can bind the target gene p38α MAPK to regulate the SGIV-induced cell apoptosis and the protease activity of caspase-3. The results indicated that SGIV infection can up-regulate the expression of E. coioides miR-122, and up-regulation of miR-122 can affect the activation of inflammatory factors, the activity of AP-1 and NF-κB, and cell apoptosis to regulate viral replication and proliferation.

Dissolution of PbS, CuS, and ZnS in oxic waters: effects of adsorbed natural organic matter - Yi-Pin Lin; I-Chia Li; Ping-I Chou (Environmental Science and Pollution Research, 2021)

Prevalence and outcomes of re-positive nucleic acid tests in discharged COVID-19 patients - Hou-wei Du; Jun-nian Chen; Xiao-bin Pan; Xiao-ling Chen; Yixian-Zhang; Shuang-fang Fang; Xiao-qing Li; Pin-cang Xia; Lei Gao; Hai-long Lin; Li-min Chen; Nan Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Advances in intervention methods and brain protection mechanisms of in situ and remote ischemic postconditioning - Chun-Yan Li; Wei Ma; Kuang-Pin Liu; Jin-Wei Yang; Xian-Bin Wang; Zhen Wu; Tong Zhang; Jia-Wei Wang; Wei Liu; Jie Liu; Yu Liang; Xing-Kui Zhang; et al. (Metabolic Brain Disease, 2021)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

Integrated control of potato late blight with a combination of the photosynthetic bacterium Rhodopseudomonas palustris strain GJ-22 and fungicides - Xin Zhang; Xiaonian Li; Yu Zhang; Yue Chen; Xinqiu Tan; Pin Su; Deyong Zhang; Yong Liu (BioControl, 2020)

Pathogenic characterization of Aeromonas salmonicida subsp. masoucida turbot isolate from China - Ping Wang; Jie Li; Tian Tian He; Nan Li; Zhao Lan Mo; Pin Nie; Hai Xia Xie (Journal of Fish Diseases, 2020)
Aeromonas salmonicida is a gram‐negative bacterium that is the causative agent of furunculosis. An A. salmonicida strain was isolated from diseased turbot ( Scophthalmus maximus ) with the sign of furunculosis from North China. Based on vapA gene, the strain was further classified as A. salmonicida subsp. masoucida RZ6S‐1. Culturing RZ6S‐1 strain at high temperature (28°C) obtained the virulence attenuated strain RZ6S. Genome sequence comparison between the two strains revealed the loss of the type IV secretion system (T4SS) and type III secretion system (T3SS) from the native plasmid pAsmB‐1 and pAsmC‐1 of wild‐type strain RZ6S‐1, respectively. Further study demonstrated that the wild‐type strain RZ6S‐1, but not its derivative mutant RZ6S, can stimulate apoptosis. Elevated protein level of cleaved caspase‐3 was detected from epithelioma papulosum cyprinid (EPC) cells infected with wild‐type strain RZ6S‐1 as compared with that infected with RZ6S strain. Meanwhile, the invasion of the mutant strain RZ6S was about 17‐fold higher than the wild‐type strain RZ6S‐1, suggesting that some protein(s) from A. salmonicida subsp. masoucida RZ6S‐1 suppress its invasion. The RZ6S mutant strain was attenuated, since its LD 50 is over 10,000 times higher compared to the wild‐type strain as revealed in the turbot infection model.

A hemizygous mutation in the androgen receptor gene causes different phenotypes of androgen insensitivity syndrome in two siblings by disrupting the nuclear translocation - Chunjie Liu; Yongfen Lyu; Pin Li (Molecular Genetics and Genomics, 2020)

Preliminary studies of hair follicle regeneration by injections of epidermal stem cells and dermal papilla cells into nude mice - Mingsheng Zhang; Yan Ye; Pin Zhao; Liming Bai; Xinping Li (Cell and Tissue Banking, 2020)
The ultimate goal of organ regenerative therapy is to reproduce fully functional organs to replace which have been damaged as a result of diseases or injury. Although several studies claimed that using different types of cells in some animal models promote hair follicles regeneration, more researches can be done to develop a sufficient and efficient protocol to induce hair generation from different animal models. In this study, we investigated the therapeutic potentials for hair follicle formation by injecting a mixture of epidermal stem cells and dermal papilla cells. Those cells were isolated and culture-expanded. Then we randomly allocated 8 nude mice into two groups. The experiment group received an injection of a mixture that containing of epidermal stem cells and dermal papilla cells. The control group received injection of keratinocyte serum-free medium. The hair follicles regeneration was observed and the injection area was harvested for HE staining. 14 day later, the regenerated hair shafts were observed and HE staining indicated that the newly hair follicle formed the correct structures in experiment group. Furthermore, the mixture injection induced a regular and multilayered stratified epidermis and the epidermis contained of hair follicle-likes structures. Our data showed that injection of a mixture of epidermal stem cells and dermal papilla cells could induce hair follicles regeneration and well-ordered epidermis formation. This study emphasized that the rearrangement of the interactions during seed cells and the niches of the seed cells is essential and necessary for tissue-engineered construct success.

Optimization of the protoplast transient expression system for gene functional studies in strawberry (Fragaria vesca) - Yi-Jie Gou; Yu-Lian Li; Pin-Pin Bi; Dan-Juan Wang; Yang-Yang Ma; Yang Hu; Hou-Cheng Zhou; Ying-Qiang Wen; Jia-Yue Feng (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

Neogenkwanine I from the flower buds of Daphne genkwa with its stereostructure confirmation using quantum calculation profiles and antitumor evaluation - Xue-Wen Hou; Shuang Han; Ying-Ying Zhang; Hai-Bi Su; Pin-Yi Gao; Ling-Zhi Li; Shao-Jiang Song (Natural Product Research, 2020)

Altered Mineral Metabolism and Disequilibrium Between Calcification Promoters and Inhibitors in Chronic Hemodialysis Patients - Chia-Liang Wang; Kuan-Pin Lin; Guoo-Shyng W. Hsu; Kai-Li Liu; Chih-Hung Guo (Biological Trace Element Research, 2020)

Critical review of ARGs reduction behavior in various sludge and sewage treatment processes in wastewater treatment plants - Gang Xue; Mingji Jiang; Hong Chen; Min Sun; Yunfan Liu; Xiang Li; Pin Gao (Critical Reviews in Environmental Science and Technology, 2019)

Evolution of Broken Coal Permeability Under the Condition of Stress, Temperature, Moisture Content, and Pore Pressure - Jiangkun Chao; Minggao Yu; Tingxiang Chu; Xuefeng Han; Fei Teng; Pin Li (Rock Mechanics and Rock Engineering, 2019)

Effects of vermicomposting on the main chemical properties and bioavailability of Cd/Zn in pure sludge - Jizhou Zhang; Maral Erdene Sugir; Yunying Li; Lei Yuan; Meng Zhou; Pin Lv; Zhimin Yu; Limin Wang; Dongxing Zhou (Environmental Science and Pollution Research, 2019)

Staphylococcal driveline infections are the predominant type of left ventricular assist device associated infections in Singapore - Yii Ean Teh; Choon Pin Lim; Louis Loon Yee Teo; Jia Lin Soon; Victor Tar Toong Chao; Chia Lee Neo; Joycelyn Li Li Tan; Ka Lee Kerk; David Kheng Leng Sim; Teing Ee Tan; Ban Hock Tan; Sivathasan Cumaraswamy; et al. (Infectious Diseases, 2019)

Magnetic Flocculation Treatment of Coal Mine Water and a Comparison of Water Quality Prediction Algorithms - Xiaohang Zhang; Xuwen He; Ming Wei; Fuqin Li; Pin Hou; Chunhui Zhang (Mine Water and the Environment, 2019)

Ecology and hydrology of early rice farming: geoarchaeological and palaeo-ecological evidence from the Late Holocene paddy field site at Maoshan, the Lower Yangtze - Yuxiang Jin; Duowen Mo; Yiyin Li; Pin Ding; Yongqiang Zong; Yijie Zhuang (Archaeological and Anthropological Sciences, 2019)

Dynamic Properties of Thermally Treated Granite Subjected to Cyclic Impact Loading - Pin Wang; Tubing Yin; Xibing Li; Shuaishuai Zhang; Lv Bai (Rock Mechanics and Rock Engineering, 2019)

Characterization of iron-metabolizing communities in soils contaminated by acid mine drainage from an abandoned coal mine in Southwest China - Pin Gao; Xiaoxu Sun; Enzong Xiao; Zhixian Xu; Baoqin Li; Weimin Sun (Environmental Science and Pollution Research, 2019)

Difference in soil bacterial community composition depends on forest type rather than nitrogen and phosphorus additions in tropical montane rainforests - Pin Li; Congcong Shen; Lai Jiang; Zhaozhong Feng; Jingyun Fang (Biology and Fertility of Soils, 2019)

Flavobacterium sharifuzzamanii sp. nov., Isolated from the Sediments of the East China Sea - Sanjit C. Debnath; Can Chen; Shu-Xia Liu; Ya-Nan Di; Dao-Qiong Zheng; Xin-Yang Li; Xue-Wei Xu; Jin-Zhong Xu; Pin-Mei Wang (Current Microbiology, 2019)

Cytochrome P450 2AA molecular clone, expression pattern, and different regulation by fish oil and lard oil in diets of grass carp (Ctenopharyngodon idella) - Xiao-chen Shi; Jian Sun; Ai Jin; Hong Ji; Hai-bo Yu; Yang Li; Xue-xian Li; Pin Liu; Chao Li; Ji-qin Huang (Fish Physiology and Biochemistry, 2018)

Responses of phytoplankton community to eutrophication in Semerak Lagoon (Malaysia) - Huey Hui Er; Li Keat Lee; Zhen Fei Lim; Sing Tung Teng; Chui Pin Leaw; Po Teen Lim (Environmental Science and Pollution Research, 2018)

Leachate phytotoxicity of flue gas desulfurization residues from coal-fired power plant - Khamphe Phoungthong; Pin-Jing He; Li-Ming Shao; Hua Zhang (Environmental Science and Pollution Research, 2018)

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Spatiotemporal patterns of drought at various time scales in Shandong Province of Eastern China - Depeng Zuo; Siyang Cai; Zongxue Xu; Fulin Li; Wenchao Sun; Xiaojing Yang; Guangyuan Kan; Pin Liu (Theoretical and Applied Climatology, 2018)

The validation of two major QTLs related to the timing of spring bud flush in Camellia sinensis - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Kang Wei; Yao Zou; Sheng-Xiang Chen; Pin-Wu Li; Qian Tang; Hao Cheng (Euphytica, 2018)

Assessing climate change adaptations for community-scale water resources using a low-frequency weather generator - Yuan-Hua Li; Ching-Pin Tung; Yuan-Hung Li; Pei-Yuan Chen (Paddy and Water Environment, 2018)

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

Three-dimensional tomography using high-power induced polarization with the similar central gradient array - Jun-Lu Wang; Pin-Rong Lin; Meng Wang; Dang Li; Jian-Hua Li (Applied Geophysics, 2017)

The death of the circulatory system diseases in China: provincial socioeconomic and environmental perspective - Haixia Pu; Jiatian Li; Pin Wang; Linlin Cui; Huaxin Wang (Environmental Science and Pollution Research, 2017)

Comparative Efficacy and Safety of Nine Anti-Platelet Therapies for Patients with Ischemic Stroke or Transient Ischemic Attack: a Mixed Treatment Comparisons - Hua-Pin Huang; Wan-Hui Lin; Sheng-Gen Chen; Li-Zhen Chen; Min-Yi Chen; Chun-Hui Che (Molecular Neurobiology, 2017)

Toxicity of butene-fipronil, in comparison with seven other insecticides, in Leptinotarsa decemlineata and Drosophila melanogaster - Muhammad Shahid Arain; Pin-Jun Wan; Muhammad Shakeel; Muhammad Farooq; Xing-Xing Hu; Syed Ali Haider Shah; Muhammad Esmail Abdalla Elzaki; Guo-Qing Li (Phytoparasitica, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

Contribution of redox-dependent activation of endothelial Nlrp3 inflammasomes to hyperglycemia-induced endothelial dysfunction - Yang Chen; Lei Wang; Ashley L. Pitzer; Xiang Li; Pin-Lan Li; Yang Zhang (Journal of Molecular Medicine, 2016)

A high throughput method for rapid screening of chitosanase-producing fungal strain under acidic conditions - Su Ding; Gui-Guang Chen; Zhi-Qun Liang; Wei Zeng; Mu-Ming Cao; Guo-Pin Chen; Shu-Yu Xie; Wei Li (World Journal of Microbiology and Biotechnology, 2016)

Determination of Dynamic Flexural Tensile Strength of Thermally Treated Laurentian Granite Using Semi-Circular Specimens - Tubing Yin; Pin Wang; Xibing Li; Bangbiao Wu; Ming Tao; Ronghua Shu (Rock Mechanics and Rock Engineering, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Resistance to Pythium irregulare root and hypocotyl disease in diverse common bean (Phaseolus vulgaris) varieties from 37 countries and relationships to waterlogging tolerance and other plant and seed traits - Yu Pin Li; Ming Pei You; Sally Norton; Martin J. Barbetti (European Journal of Plant Pathology, 2016)

Contribution of aboveground litter to soil respiration in Populus davidiana Dode plantations at different stand ages - Xin Zhao; Fa-dong Li; Wan-jun Zhang; Zhi-pin Ai (Journal of Mountain Science, 2016)

Separation, determination and antifungal activity test of the products from a new Bacillus amyloliquefaciens - Tao Wang; Mian-Bin Wu; Zheng-Jie Chen; Jian-Pin Lin; Li-Rong Yang (Natural Product Research, 2016)

Inhibition effects of high calcium concentration on anaerobic biological treatment of MSW leachate - Yi Xia; Pin-Jing He; Hong-Xia Pu; Fan Lü; Li-Ming Shao; Hua Zhang (Environmental Science and Pollution Research, 2016)

Landfill Risk Assessment on Groundwater Based on Vulnerability and Pollution Index - Bo Zhang; Guoxiu Li; Pin Cheng; Tian-Chyi Jim Yeh; Mei Hong (Water Resources Management, 2016)

Spatial optimization procedure for land-use arrangement in a community based on a human comfort perspective - Pei-Yuan Chen; Ching-Pin Tung; Wei-Chih Lin; Yuan-Hua Li (Paddy and Water Environment, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Ontogenetic development of adipose tissue in grass carp (Ctenopharyngodon idellus) - Pin Liu; Hong Ji; Chao Li; Jingjing Tian; Yifei Wang; Ping Yu (Fish Physiology and Biochemistry, 2015)

The potential roles of bacterial communities in coral defence: A case study at Talang-talang reef - Felicity W. I. Kuek; Li-Fang Lim; Lin-Hui Ngu; Aazani Mujahid; Po-Teen Lim; Chui-Pin Leaw; Moritz Müller (Ocean Science Journal, 2015)

CARD9 Deficiencies Linked to Impaired Neutrophil Functions Against Phialophora verrucosa - Pin Liang; Xiaowen Wang; Runchao Wang; Zhe Wan; Wenling Han; Ruoyu Li (Mycopathologia, 2015)

Acid sphingomyelinase inhibition protects mice from lung edema and lethal Staphylococcus aureus sepsis - Huiming Peng; Cao Li; Stephanie Kadow; Brian D. Henry; Jörg Steinmann; Katrin Anne Becker; Andrea Riehle; Natalie Beckmann; Barbara Wilker; Pin-Lan Li; Timothy Pritts; Michael J. Edwards; et al. (Journal of Molecular Medicine, 2015)

Streptomycin Ototoxicity in Rat Cochlear Organotypic Cultures - Jing-chun He; Miao-miao Han; Ke-yong Li; Pin Dong (Cell Biochemistry and Biophysics, 2015)

A novel SMAD family protein, SMAD9 is involved in follicular initiation and changes egg yield of geese via synonymous mutations in exon1 and intron2 - Jun Xu; Jun Li; Haosen Wang; Guanglin Wang; Jie Chen; Pin Huang; Jienan Cheng; Lu Gan; Zhao Wang; Yafei Cai (Molecular Biology Reports, 2015)

Integrated water resources system dynamics modeling and indicators for sustainable rural community - Yuan-Hua Li; Pei-Yuan Chen; Wei-Hsuan Lo; Ching-Pin Tung (Paddy and Water Environment, 2015)

Distribution of enterovirus 71 RNA in inflammatory cells infiltrating different tissues in fatal cases of hand, foot, and mouth disease - Pin Yu; Zifen Gao; Yuanyuan Zong; Linlin Bao; Lili Xu; Wei Deng; Yanfeng Xu; Zhancheng Gao; Yanfeng Yao; Fengdi Li; Qi Lv; Chuan Qin (Archives of Virology, 2015)

The evolution of permeability and gas composition during remote protective longwall mining and stress-relief gas drainage: a case study of the underground Haishiwan Coal Mine - Wei Li; Yuan-ping Cheng; Pin-kun Guo; Feng-hua An; Ming-yi Chen (Geosciences Journal, 2014)

Transplantation of mesenchymal stem cells into the renal medulla attenuated salt-sensitive hypertension in Dahl S rat - Junping Hu; Qing Zhu; Min Xia; Tai L. Guo; Zhengchao Wang; Pin-Lan Li; Wei-Qing Han; Fan Yi; Ningjun Li (Journal of Molecular Medicine, 2014)

Cadmium Neurotoxicity to a Freshwater Planarian - Jui-Pin Wu; Hui-Ling Lee; Mei-Hui Li (Archives of Environmental Contamination and Toxicology, 2014)

Regulation of adipocytes lipolysis by n-3 HUFA in grass carp (Ctenopharyngodon idellus) in vitro and in vivo - Pin Liu; Chao Li; Jiqin Huang; Hong Ji (Fish Physiology and Biochemistry, 2014)

The complete mitochondrial genome of the brown leg mite, Aleuroglyphus ovatus (Acari: Sarcoptiformes): evaluation of largest non-coding region and unique tRNAs - En-Tao Sun; Chao-Pin Li; Liu-Wang Nie; Yu-Xin Jiang (Experimental and Applied Acarology, 2014)

Global patterns of soil microbial nitrogen and phosphorus stoichiometry in forest ecosystems - Pin Li; Yuanhe Yang; Wenxuan Han; Jingyun Fang (Global Ecology and Biogeography, 2014)
Aim To investigate broad‐scale patterns of soil microbial nitrogen ( N ) and phosphorus ( P ) stoichiometry and their environmental drivers. Location Global forests. Methods By synthesizing 652 observations of soil microbial biomass N and P derived from the published literature, we investigated global patterns of soil microbial N , P and N : P ratios and their relationships with climate, soil and vegetation types. Results Microbial N and P concentrations varied widely among forest types, with relatively low N and P concentrations but high N : P ratios in tropical forests. The N and P concentrations increased and the N : P ratio decreased with increasing latitude (or decreasing temperature). The N:P ratio showed a similar pattern along the precipitation gradient to that along the temperature gradient, whereas microbial N and P displayed weak trends along the precipitation gradient. Edaphic variables also regulated the patterns of microbial N and P stoichiometry: microbial N and P concentrations increased with soil N and P concentrations as well as with soil pH . Mixed‐effects models revealed that edaphic factors explained the largest part of the variation in microbial N , P and the N : P ratio, suggesting their dominant role. Main conclusions Our findings highlight that there are broad‐scale patterns in microbial N , P and the N : P ratio along the gradients of latitude, temperature and precipitation, which are similar to those reported in plants and soils. The consistency of these patterns in plant–soil–microbe ecosystems supports the hypothesis that P is more often the major limiting element at low latitudes than at high latitudes.

Stoichiometric shifts in surface soils over broad geographical scales: evidence from C hina's grasslands - Yuanhe Yang; Jingyun Fang; Chengjun Ji; Arindam Datta; Pin Li; Wenhong Ma; Anwar Mohammat; Haihua Shen; Huifeng Hu; Benjamin O. Knapp; Pete Smith (Global Ecology and Biogeography, 2014)
Aim The identification of stoichiometric flexibility is crucial for understanding carbon–nitrogen–phosphorus ( C – N – P ) interactions and ecosystem dynamics under a changing environment. However, current evidence of stoichiometric flexibility mainly comes from manipulation experiments, with little evidence from large‐scale observations. Location Alpine and temperate grasslands across northern C hina. Methods Using soil profiles derived from a historical national soil inventory and a contemporary regional soil survey across C hina's grasslands, we examined temporal changes in topsoil C : N : P ratios over recent decades. Results Topsoil C:N ratios of five major grassland types exhibited some flexibility but did not show significant changes over the sampling interval. Non‐significant changes in topsoil C : N ratios were observed both in alpine grasslands on the T ibetan P lateau and in temperate grasslands on the Inner Mongolian Plateau. Consistent with the relatively stable C : N ratios, the slope of the soil C – N stoichiometric relationship did not differ significantly between the two sampling periods. Soil N:P ratios in the surface layer increased significantly over the sampling interval, however, with an overall increase of 0.60 (95% confidence interval 0.58–0.62). A larger increase in soil N : P ratio was found in temperate grasslands on the I nner M ongolian P lateau than in alpine grasslands on the T ibetan P lateau. Moreover, the slope of the soil N – P stoichiometric relationship in these grassland ecosystems became steeper over the sampling interval. Main conclusions These results demonstrate the stability of topsoil C : N stoichiometry but variability in N : P stoichiometry over broad geographical scales, highlighting that soil C and N are tightly coupled, but N and P tend to be decoupled under a changing environment.

Increased topsoil carbon stock across China's forests - Yuanhe Yang; Pin Li; Jinzhi Ding; Xia Zhao; Wenhong Ma; Chengjun Ji; Jingyun Fang (Global Change Biology, 2014)
Biomass carbon accumulation in forest ecosystems is a widespread phenomenon at both regional and global scales. However, as coupled carbon–climate models predicted, a positive feedback could be triggered if accelerated soil carbon decomposition offsets enhanced vegetation growth under a warming climate. It is thus crucial to reveal whether and how soil carbon stock in forest ecosystems has changed over recent decades. However, large‐scale changes in soil carbon stock across forest ecosystems have not yet been carefully examined at both regional and global scales, which have been widely perceived as a big bottleneck in untangling carbon–climate feedback. Using newly developed database and sophisticated data mining approach, here we evaluated temporal changes in topsoil carbon stock across major forest ecosystem in China and analysed potential drivers in soil carbon dynamics over broad geographical scale. Our results indicated that topsoil carbon stock increased significantly within all of five major forest types during the period of 1980s–2000s, with an overall rate of 20.0 g C m −2 yr −1 (95% confidence interval, 14.1–25.5). The magnitude of soil carbon accumulation across coniferous forests and coniferous/broadleaved mixed forests exhibited meaningful increases with both mean annual temperature and precipitation. Moreover, soil carbon dynamics across these forest ecosystems were positively associated with clay content, with a larger amount of SOC accumulation occurring in fine‐textured soils. In contrast, changes in soil carbon stock across broadleaved forests were insensitive to either climatic or edaphic variables. Overall, these results suggest that soil carbon accumulation does not counteract vegetation carbon sequestration across China's forest ecosystems. The combination of soil carbon accumulation and vegetation carbon sequestration triggers a negative feedback to climate warming, rather than a positive feedback predicted by coupled carbon–climate models.

Oxidative Stress and Autophagic Alteration in Brainstem of SOD1-G93A Mouse Model of ALS - Ting An; Pengxiao Shi; Weisong Duan; Shipan Zhang; Pin Yuan; Zhongyao Li; Dongxia Wu; Zuoshang Xu; Chunyan Li; Yansu Guo (Molecular Neurobiology, 2014)

Feather Keratin Deposits as Biosorbent for the Removal of Methylene Blue from Aqueous Solution: Equilibrium, Kinetics, and Thermodynamics Studies - Pin Gao; Kanzhu Li; Zhenhong Liu; Baojiang Liu; Chunyan Ma; Gang Xue; Meihua Zhou (Water, Air, & Soil Pollution, 2014)

Control of autophagy maturation by acid sphingomyelinase in mouse coronary arterial smooth muscle cells: protective role in atherosclerosis - Xiang Li; Ming Xu; Ashley L. Pitzer; Min Xia; Krishna M. Boini; Pin-Lan Li; Yang Zhang (Journal of Molecular Medicine, 2014)

Development of a loop-mediated isothermal amplification method for rapid detection of pigeon circovirus - Shinn Shyong Tsai; Yeng Ling Chang; Yen Li Huang; Hung Jen Liu; Guan Ming Ke; Chwei Jang Chiou; Yao Ching Hsieh; Tsung Chou Chang; Li Ting Cheng; Kuo Pin Chuang (Archives of Virology, 2014)

Nod-Like Receptor Protein 1 Inflammasome Mediates Neuron Injury under High Glucose - Xian-Fang Meng; Xiao-Lan Wang; Xiu-Juan Tian; Zhi-Hua Yang; Guang-Pin Chu; Jing Zhang; Man Li; Jing Shi; Chun Zhang (Molecular Neurobiology, 2014)

Fluid inclusion and H–O–C isotope geochemistry of the Yaochong porphyry Mo deposit in Dabie Shan, China: a case study of porphyry systems in continental collision orogens - Pin Wang; Yan-Jing Chen; Bin Fu; Yong-Fei Yang; Mei Mi; Zhong-Lie Li (International Journal of Earth Sciences, 2014)

Activation of mammalian target of rapamycin contributes to pain nociception induced in rats by BmK I, a sodium channel-specific modulator - Feng Jiang; Li-Ming Hua; Yun-Lu Jiao; Pin Ye; Jin Fu; Zhi-Jun Cheng; Gang Ding; Yong-Hua Ji (Neuroscience Bulletin, 2014)

MicroRNA-124 (miR-124) Regulates Ku70 Expression and is Correlated with Neuronal Death Induced by Ischemia/Reperfusion - Fei Zhu; Jing-Li Liu; Jing-Pin Li; Fang Xiao; Zhao-Xia Zhang; Lei Zhang (Journal of Molecular Neuroscience, 2014)

Spatio-temporal changes in biomass carbon sinks in China’s forests from 1977 to 2008 - ZhaoDi Guo; HuiFeng Hu; Pin Li; NuYun Li; JingYun Fang (Science China Life Sciences, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

Protective role of growth hormone against hyperhomocysteinemia-induced glomerular injury - Caixia Li; Min Xia; Justine M. Abais; Xiaocheng Liu; Ningjun Li; Krishna M. Boini; Pin-Lan Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Cordyceps sinensis protects against renal ischemia/reperfusion injury in rats - Hua-Pin Wang; Ching-Wen Liu; Hsueh-Wen Chang; Jen-Wei Tsai; Ya-Zhu Sung; Li-Ching Chang (Molecular Biology Reports, 2013)

TRAIL death receptor 4 signaling via lysosome fusion and membrane raft clustering in coronary arterial endothelial cells: evidence from ASM knockout mice - Xiang Li; Wei-Qing Han; Krishna M. Boini; Min Xia; Yang Zhang; Pin-Lan Li (Journal of Molecular Medicine, 2013)

Bioaccumulation and Toxicodynamics of Cadmium to Freshwater Planarian and the Protective Effect of N-Acetylcysteine - Jui-Pin Wu; Hon-Cheng Chen; Mei-Hui Li (Archives of Environmental Contamination and Toxicology, 2012)

Increased susceptibility of algal symbionts to photo-inhibition resulting from the perturbation of coral gastrodermal membrane trafficking - Chii-Shiarng Chen; Shih-Pin Yeh; Li-Hsueh Wang; Hsing-Hui Li; Uang Wan-Nan Chen (Science China Life Sciences, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Exocytosis of SH-SY5Y single cell with different shapes cultured on ITO micro-pore electrode - Hui Zhao; Ling Li; Hua-Jun Fan; Fei Wang; Li-Ming Jiang; Pin-Gang He; Yu-Zhi Fang (Molecular and Cellular Biochemistry, 2012)

Down-Regulation of Tumor-Associated NADH Oxidase, tNOX (ENOX2), Enhances Capsaicin-Induced Inhibition of Gastric Cancer Cell Growth - His-Ming Wang; Show-Mei Chuang; Yu-Ching Su; Yi-Hui Li; Pin Ju Chueh (Cell Biochemistry and Biophysics, 2011)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

Epithelial-to-mesenchymal transition in podocytes mediated by activation of NADPH oxidase in hyperhomocysteinemia - Chun Zhang; Min Xia; Krishna M. Boini; Cai-Xia Li; Justine M. Abais; Xiao-Xue Li; Laura A. Laperle; Pin-Lan Li (Pflügers Archiv - European Journal of Physiology, 2011)

A novel strategy to derive iPS cells from porcine fibroblasts - WeiMin Ruan; JianYong Han; Pin Li; SuYing Cao; Yang An; Bing Lim; Ning Li (Science China Life Sciences, 2011)

Rescue of Newcastle disease virus from cloned cDNA using an RNA polymerase II promoter - Bao-yu Li; Xue-rui Li; Xi Lan; Xiang-pin Yin; Zhi-yong Li; Bin Yang; Ji-xing Liu (Archives of Virology, 2011)

Development and application of RAPD-SCAR markers to identify intra-species hybrids of industrial Saccharomyces cerevisiae - Pin-Mei Wang; Xue-Chang Wu; Xiao-Qin Chi; Yu-Dong Li; Dao-Qiong Zheng; Rui Ding; Hang Min (World Journal of Microbiology and Biotechnology, 2011)

α-Mangostin Suppresses Phorbol 12-myristate 13-acetate-Induced MMP-2/MMP-9 Expressions via αvβ3 Integrin/FAK/ERK and NF-κB Signaling Pathway in Human Lung Adenocarcinoma A549 Cells - Yuan-Wei Shih; Shang-Tao Chien; Pin-Shern Chen; Jian-Hui Lee; Shu-Hau Wu; Li-Te Yin (Cell Biochemistry and Biophysics, 2010)

Construction and Characterization of a Bacterial Artificial Chromosome (BAC) Library of Pacific White Shrimp, Litopenaeus vannamei - Xiaojun Zhang; Yang Zhang; Chantel Scheuring; Hong-Bin Zhang; Pin Huan; Bing Wang; Chengzhang Liu; Fuhua Li; Bin Liu; Jianhai Xiang (Marine Biotechnology, 2010)

Interval number fuzzy linear programming for climate change impact assessments of reservoir active storage - Ching-Pin Tung; Nien-Ming Hong; Ming-hsu Li (Paddy and Water Environment, 2009)

Assessing the impact of climate change on the land hydrology in Taiwan - Ming-Hsu Li; Waiting Tien; Ching-Pin Tung (Paddy and Water Environment, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Construction and Characterization of Two Bacterial Artificial Chromosome Libraries of Zhikong Scallop, Chlamys farreri Jones et Preston, and Identification of BAC Clones Containing the Genes Involved in Its Innate Immune System - Yang Zhang; Xiaojun Zhang; Chantel F. Scheuring; Hong-Bin Zhang; Pin Huan; Fuhua Li; Jianhai Xiang (Marine Biotechnology, 2008)

Detailed Pollution Map of an Area Highly Contaminated by Mercury Containing Wastewater from an Organic Chemical Factory in People's Republic of China - A. Matsuyama; Y. Yasuda; A. Yasutake; L. Xiaojie; J. Pin; L. Li; L. Mei; A. Yumin; Q. Liya (Bulletin of Environmental Contamination and Toxicology, 2006)

Relationship Between Leached Total Mercury and Leached Methylmercury from Soil Polluted by Mercury in Wastewater from an Organic Chemical Factory in the People’s Republic of China - A. Matsuyama; Y. Yasuda; A. Yasutake; L. Xiaojie; J. Pin; L. Li; L. Mei; A. Yumin; Q. Liya (Bulletin of Environmental Contamination and Toxicology, 2005)

Hydrogenation properties of mechanically milled Mg2Ni0.8Cr0.2-CoO/Al2O3 composites - Xiu-li Wang; Jiang-ping Tu; Chang-pin Chen; Xiao-bin Zhang; Xin-bing Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

Distribution of Methylmercury in an Area Polluted by Mercury Containing Wastewater from an Organic Chemical Factory in China - A. Matsuyama; Q. Liya; A. Yasutake; M. Yamaguchi; R. Aramaki; L. Xiaojie; J. Pin; L. Li; L. Mei; A. Yumin; Y. Yasuda (Bulletin of Environmental Contamination and Toxicology, 2004)

Mercury Distribution in Farmlands Downstream from an Acetaldehyde Producing Chemical Company in Qingzhen City, Guizhou, People?s Republic of China - Y. Yasuda; A. Matsuyama; A. Yasutake; M. Yamaguchi; R. Aramaki; L. Xiaojie; J. Pin; A. Yumin; L. Li; L. Mei; C. Wei; Q. Liya (Bulletin of Environmental Contamination and Toxicology, 2004)

A G-Quadruplex Ligand 3,3′-Diethyloxadicarbocyanine Iodide Induces Mitochondrion-Mediated Apoptosis But Not Decrease of Telomerase Activity in Nasopharyngeal Carcinoma NPC-TW01 Cells - Chung-Pin Li; Jen-Hsin Huang; Ai-Chi Chang; Yi-Mei Hung; Chao-Hsiung Lin; Yee Chao; Shou-Dong Lee; Jacqueline Whang-Peng; Tze-Sing Huang (Pharmaceutical Research, 2004)

Measurement of Orientation and Distribution of Cellular Alignment and Cytoskeletal Organization - William J. Karlon; Pin-Pin Hsu; Song Li; Shu Chien; Andrew D. McCulloch; Jeffrey H. Omens (Annals of Biomedical Engineering, 1999)